Algorithms for algebraic path properties in concurrent systems of constant treewidth components - Chatterjee, Krishnendu; Ibsen-Jensen, Rasmus; Goharshady, Amir; Pavlogiannis, Andreas
We study algorithmic questions for concurrent systems where the transitions are labeled from a complete, closed semiring, and path properties are algebraic with semiring operations. The algebraic path properties can model dataflow analysis problems, the shortest path problem, and many other natural problems that arise in program analysis. We consider that each component of the concurrent system is a graph with constant treewidth, a property satisfied by the controlflow graphs of most programs. We allow for multiple possible queries, which arise naturally in demand driven dataflow analysis. The study of multiple queries allows us to consider the tradeoff between the resource usage of the one-time preprocessing and for each individual query. The traditional approach constructs the product graph of all components and applies the best-known graph algorithm on the product. In this approach, even the answer to a single query requires the transitive closure (i.e., the results of all possible queries), which provides no room for tradeoff between preprocessing and query time. Our main contributions are algorithms that significantly improve the worst-case running time of the traditional approach, and provide various tradeoffs depending on the number of queries. For example, in a concurrent system of two components, the traditional approach requires hexic time in the worst case for answering one query as well as computing the transitive closure, whereas we show that with one-time preprocessing in almost cubic time, each subsequent query can be answered in at most linear time, and even the transitive closure can be computed in almost quartic time. Furthermore, we establish conditional optimality results showing that the worst-case running time of our algorithms cannot be improved without achieving major breakthroughs in graph algorithms (i.e., improving the worst-case bound for the shortest path problem in general graphs). Preliminary experimental results show that our algorithms perform favorably on several benchmarks.

Algorithms for algebraic path properties in concurrent systems of constant treewidth components - Anonymous, 1; Anonymous, 2; Anonymous, 3; Anonymous, 4
We study algorithmic questions for concurrent systems where the transitions are labeled from a complete, closed semiring, and path properties are algebraic with semiring operations. The algebraic path properties can model dataflow analysis problems, the shortest path problem, and many other natural properties that arise in program analysis. We consider that each component of the concurrent system is a graph with constant treewidth, and it is known that the controlflow graphs of most programs have constant treewidth. We allow for multiple possible queries, which arise naturally in demand driven dataflow analysis problems (e.g., alias analysis). The study of multiple queries allows us to consider the tradeoff between the resource usage of the one-time preprocessing and for each individual query. The traditional approaches construct the product graph of all components and apply the best-known graph algorithm on the product. In the traditional approach, even the answer to a single query requires the transitive closure computation (i.e., the results of all possible queries), which provides no room for tradeoff between preprocessing and query time. Our main contributions are algorithms that significantly improve the worst-case running time of the traditional approach, and provide various tradeoffs depending on the number of queries. For example, in a concurrent system of two components, the traditional approach requires hexic time in the worst case for answering one query as well as computing the transitive closure, whereas we show that with one-time preprocessing in almost cubic time, each subsequent query can be answered in at most linear time, and even the transitive closure can be computed in almost quartic time. Furthermore, we establish conditional optimality results that show that the worst-case running times of our algorithms cannot be improved without achieving major breakthroughs in graph algorithms (such as improving the worst-case bounds for the shortest path problem in general graphs whose current best-known bound has not been improved in five decades). Finally, we provide a prototype implementation of our algorithms which significantly outperforms the existing algorithmic methods on several benchmarks.

Temporal logic control for stochastic linear systems using abstraction refinement of probabilistic games - Svoreňová, Mária; Kretinsky, Jan; Chmelik, Martin; Chatterjee, Krishnendu; Cěrná, Ivana; Belta, Cǎlin (Proceedings of the 18th International Conference on Hybrid Systems: Computation and Control)
We consider the problem of computing the set of initial states of a dynamical system such that there exists a control strategy to ensure that the trajectories satisfy a temporal logic specification with probability 1 (almost-surely). We focus on discrete-time, stochastic linear dynamics and specifications given as formulas of the Generalized Reactivity(1) fragment of Linear Temporal Logic over linear predicates in the states of the system. We propose a solution based on iterative abstraction-refinement, and turn-based 2-player probabilistic games. While the theoretical guarantee of our algorithm after any finite number of iterations is only a partial solution, we show that if our algorithm terminates, then the result is the set of satisfying initial states. Moreover, for any (partial) solution our algorithm synthesizes witness control strategies to ensure almost-sure satisfaction of the temporal logic specification. We demonstrate our approach on an illustrative case study.

Model checking gene regulatory networks - Giacobbe, Mirco; Guet, Calin C; Gupta, Ashutosh; Henzinger, Thomas A; Paixao, Tiago; Petrov, Tatjana
The behaviour of gene regulatory networks (GRNs) is typically analysed using simulation-based statistical testing-like methods. In this paper, we demonstrate that we can replace this approach by a formal verification-like method that gives higher assurance and scalability. We focus on Wagner’s weighted GRN model with varying weights, which is used in evolutionary biology. In the model, weight parameters represent the gene interaction strength that may change due to genetic mutations. For a property of interest, we synthesise the constraints over the parameter space that represent the set of GRNs satisfying the property. We experimentally show that our parameter synthesis procedure computes the mutational robustness of GRNs –an important problem of interest in evolutionary biology– more efficiently than the classical simulation method. We specify the property in linear temporal logics. We employ symbolic bounded model checking and SMT solving to compute the space of GRNs that satisfy the property, which amounts to synthesizing a set of linear constraints on the weights.

Embryo-lethal phenotypes in early abp1 mutants are due to disruption of the neighboring BSM gene - Michalko, Jaroslav; Dravecka, Marta; Bollenbach, Tobias; Friml, Jirí (F1000 Research)
The Auxin Binding Protein1 (ABP1) has been identified based on its ability to bind auxin with high affinity and studied for a long time as a prime candidate for the extracellular auxin receptor responsible for mediating in particular the fast non-transcriptional auxin responses. However, the contradiction between the embryo-lethal phenotypes of the originally described Arabidopsis T-DNA insertional knock-out alleles (abp1-1 and abp1-1s) and the wild type-like phenotypes of other recently described loss-of-function alleles (abp1-c1 and abp1-TD1) questions the biological importance of ABP1 and relevance of the previous genetic studies. Here we show that there is no hidden copy of the ABP1 gene in the Arabidopsis genome but the embryo-lethal phenotypes of abp1-1 and abp1-1s alleles are very similar to the knock-out phenotypes of the neighboring gene, BELAYA SMERT (BSM). Furthermore, the allelic complementation test between bsm and abp1 alleles shows that the embryo-lethality in the abp1-1 and abp1-1s alleles is caused by the off-target disruption of the BSM locus by the T-DNA insertions. This clarifies the controversy of different phenotypes among published abp1 knock-out alleles and asks for reflections on the developmental role of ABP1.

Evolution of decisions in population games with sequentially searching individuals - Priklopil, Tadeas; Chatterjee, Krishnendu (Games)
In many social situations, individuals endeavor to find the single best possible partner, but are constrained to evaluate the candidates in sequence. Examples include the search for mates, economic partnerships, or any other long-term ties where the choice to interact involves two parties. Surprisingly, however, previous theoretical work on mutual choice problems focuses on finding equilibrium solutions, while ignoring the evolutionary dynamics of decisions. Empirically, this may be of high importance, as some equilibrium solutions can never be reached unless the population undergoes radical changes and a sufficient number of individuals change their decisions simultaneously. To address this question, we apply a mutual choice sequential search problem in an evolutionary game-theoretical model that allows one to find solutions that are favored by evolution. As an example, we study the influence of sequential search on the evolutionary dynamics of cooperation. For this, we focus on the classic snowdrift game and the prisoner’s dilemma game.

Quantifying emergent behavior of autonomous robots - Martius, Georg S; Olbrich, Eckehard (Entropy)
Quantifying behaviors of robots which were generated autonomously from task-independent objective functions is an important prerequisite for objective comparisons of algorithms and movements of animals. The temporal sequence of such a behavior can be considered as a time series and hence complexity measures developed for time series are natural candidates for its quantification. The predictive information and the excess entropy are such complexity measures. They measure the amount of information the past contains about the future and thus quantify the nonrandom structure in the temporal sequence. However, when using these measures for systems with continuous states one has to deal with the fact that their values will depend on the resolution with which the systems states are observed. For deterministic systems both measures will diverge with increasing resolution. We therefore propose a new decomposition of the excess entropy in resolution dependent and resolution independent parts and discuss how they depend on the dimensionality of the dynamics, correlations and the noise level. For the practical estimation we propose to use estimates based on the correlation integral instead of the direct estimation of the mutual information based on next neighbor statistics because the latter allows less control of the scale dependencies. Using our algorithm we are able to show how autonomous learning generates behavior of increasing complexity with increasing learning duration.

Low-dose sevoflurane promoteshippocampal neurogenesis and facilitates the development of dentate gyrus-dependent learning in neonatal rats - Chen, Chong; Wang, Chao; Zhao, Xuan; Zhou, Tao; Xu, Dao; Wang, Zhi; Wang, Ying (ASN Neuro)
Huge body of evidences demonstrated that volatile anesthetics affect the hippocampal neurogenesis and neurocognitive functions, and most of them showed impairment at anesthetic dose. Here, we investigated the effect of low dose (1.8%) sevoflurane on hippocampal neurogenesis and dentate gyrus-dependent learning. Neonatal rats at postnatal day 4 to 6 (P4-6) were treated with 1.8% sevoflurane for 6 hours. Neurogenesis was quantified by bromodeoxyuridine labeling and electrophysiology recording. Four and seven weeks after treatment, the Morris water maze and contextual-fear discrimination learning tests were performed to determine the influence on spatial learning and pattern separation. A 6-hour treatment with 1.8% sevoflurane promoted hippocampal neurogenesis and increased the survival of newborn cells and the proportion of immature granular cells in the dentate gyrus of neonatal rats. Sevoflurane-treated rats performed better during the training days of the Morris water maze test and in contextual-fear discrimination learning test. These results suggest that a subanesthetic dose of sevoflurane promotes hippocampal neurogenesis in neonatal rats and facilitates their performance in dentate gyrus-dependent learning tasks.

Discrete Ricci curvature bounds for Bernoulli-Laplace and random transposition models - Erbar, Matthias; Maas, Jan; Tetali, Prasad (Annales de la faculté des sciences de Toulouse)
We calculate a Ricci curvature lower bound for some classical examples of random walks, namely, a chain on a slice of the n-dimensional discrete cube (the so-called Bernoulli-Laplace model) and the random transposition shuffle of the symmetric group of permutations on n letters.

Efficient production of single-stranded phage DNA as scaffolds for DNA origami - Kick, B; Praetorius, Florian M; Dietz, H; Weuster-Botz, D (Nano Letters)
Scaffolded DNA origami enables the fabrication of a variety of complex nanostructures that promise utility in diverse fields of application, ranging from biosensing over advanced therapeutics to metamaterials. The broad applicability of DNA origami as a material beyond the level of proof-of-concept studies critically depends, among other factors, on the availability of large amounts of pure single-stranded scaffold DNA. Here, we present a method for the efficient production of M13 bacteriophage-derived genomic DNA using high-cell-density fermentation of Escherichia coli in stirred-tank bioreactors. We achieve phage titers of up to 1.6 × 1014 plaque-forming units per mL. Downstream processing yields up to 410 mg of high-quality single-stranded DNA per one liter reaction volume, thus upgrading DNA origami-based nanotechnology from the milligram to the gram scale.

Counterexample explanation by learning small strategies in Markov decision processes - Brázdil, Tomáš; Chatterjee, Krishnendu; Chmelik, Martin; Fellner, Andreas; Kretinsky, Jan
For deterministic systems, a counterexample to a property can simply be an error trace, whereas counterexamples in probabilistic systems are necessarily more complex. For instance, a set of erroneous traces with a sufficient cumulative probability mass can be used. Since these are too large objects to understand and manipulate, compact representations such as subchains have been considered. In the case of probabilistic systems with non-determinism, the situation is even more complex. While a subchain for a given strategy (or scheduler, resolving non-determinism) is a straightforward choice, we take a different approach. Instead, we focus on the strategy itself, and extract the most important decisions it makes, and present its succinct representation. The key tools we employ to achieve this are (1) introducing a concept of importance of a state w.r.t. the strategy, and (2) learning using decision trees. There are three main consequent advantages of our approach. Firstly, it exploits the quantitative information on states, stressing the more important decisions. Secondly, it leads to a greater variability and degree of freedom in representing the strategies. Thirdly, the representation uses a self-explanatory data structure. In summary, our approach produces more succinct and more explainable strategies, as opposed to e.g. binary decision diagrams. Finally, our experimental results show that we can extract several rules describing the strategy even for very large systems that do not fit in memory, and based on the rules explain the erroneous behaviour.

Experimental part of CAV 2015 publication: Counterexample Explanation by Learning Small Strategies in Markov Decision Processes - Fellner, Andreas
This repository contains the experimental part of the CAV 2015 publication Counterexample Explanation by Learning Small Strategies in Markov Decision Processes. We extended the probabilistic model checker PRISM to represent strategies of Markov Decision Processes as Decision Trees. The archive contains a java executable version of the extended tool (prism_dectree.jar) together with a few examples of the PRISM benchmark library. To execute the program, please have a look at the README.txt, which provides instructions and further information on the archive. The archive contains scripts that (if run often enough) reproduces the data presented in the publication.
Keywords: Markov Decision Process; Decision Tree; Probabilistic Verification; Counterexample Explanation

Bounding Helly numbers via Betti numbers - Goaoc, Xavier; Paták, Pavel; Patakova, Zuzana; Tancer, Martin; Wagner, Uli
We show that very weak topological assumptions are enough to ensure the existence of a Helly-type theorem. More precisely, we show that for any non-negative integers b and d there exists an integer h(b,d) such that the following holds. If F is a finite family of subsets of R^d such that the ith reduced Betti number (with Z_2 coefficients in singular homology) of the intersection of any proper subfamily G of F is at most b for every non-negative integer i less or equal to (d-1)/2, then F has Helly number at most h(b,d). These topological conditions are sharp: not controlling any of these first Betti numbers allow for families with unbounded Helly number. Our proofs combine homological non-embeddability results with a Ramsey-based approach to build, given an arbitrary simplicial complex K, some well-behaved chain map from C_*(K) to C_*(R^d). Both techniques are of independent interest.

Improvements in Birch's theorem on forms in many variables - Browning, Timothy D; Prendiville, Sean (Journal fur die Reine und Angewandte Mathematik)
We show that a non-singular integral form of degree d is soluble non-trivially over the integers if and only if it is soluble non-trivially over the reals and the p-adic numbers, provided that the form has at least (d-\sqrt{d}/2)2^d variables. This improves on a longstanding result of Birch.

Proofs of space - Dziembowski, Stefan; Faust, Sebastian; Kolmogorov, Vladimir; Pietrzak, Krzysztof Z (35th Annual Cryptology Conference)
Proofs of work (PoW) have been suggested by Dwork and Naor (Crypto’92) as protection to a shared resource. The basic idea is to ask the service requestor to dedicate some non-trivial amount of computational work to every request. The original applications included prevention of spam and protection against denial of service attacks. More recently, PoWs have been used to prevent double spending in the Bitcoin digital currency system. In this work, we put forward an alternative concept for PoWs - so-called proofs of space (PoS), where a service requestor must dedicate a significant amount of disk space as opposed to computation. We construct secure PoS schemes in the random oracle model (with one additional mild assumption required for the proof to go through), using graphs with high “pebbling complexity” and Merkle hash-trees. We discuss some applications, including follow-up work where a decentralized digital currency scheme called Spacecoin is constructed that uses PoS (instead of wasteful PoW like in Bitcoin) to prevent double spending. The main technical contribution of this work is the construction of (directed, loop-free) graphs on N vertices with in-degree O(log logN) such that even if one places Θ(N) pebbles on the nodes of the graph, there’s a constant fraction of nodes that needs Θ(N) steps to be pebbled (where in every step one can put a pebble on a node if all its parents have a pebble).

Cancer/Testis antigen PASD1 silences the circadian clock - Michael, Alicia Kathleen; Harvey, Stacy L.; Sammons, Patrick J.; Anderson, Amanda P.; Kopalle, Hema M.; Banham, Alison H.; Partch, Carrie L. (Molecular Cell)
The circadian clock orchestrates global changes in transcriptional regulation on a daily basis via the bHLH-PAS transcription factor CLOCK:BMAL1. Pathways driven by other bHLH-PAS transcription factors have a homologous repressor that modulates activity on a tissue-specific basis, but none have been identified for CLOCK:BMAL1. We show here that the cancer/testis antigen PASD1 fulfills this role to suppress circadian rhythms. PASD1 is evolutionarily related to CLOCK and interacts with the CLOCK:BMAL1 complex to repress transcriptional activation. Expression of PASD1 is restricted to germline tissues in healthy individuals but can be induced in cells of somatic origin upon oncogenic transformation. Reducing PASD1 in human cancer cells significantly increases the amplitude of transcriptional oscillations to generate more robust circadian rhythms. Our results describe a function for a germline-specific protein in regulation of the circadian clock and provide a molecular link from oncogenic transformation to suppression of circadian rhythms.
Keywords: Cell Biology; Molecular Biology

Quantifying the determinants of evolutionary dynamics leading to drug resistance - Chevereau, Guillaume; Dravecka, Marta; Batur, Tugce; Guvenek, Aysegul; Ayhan, Dilay; Toprak, Erdal; Bollenbach, Mark Tobias (PLoS Biology)
The emergence of drug resistant pathogens is a serious public health problem. It is a long-standing goal to predict rates of resistance evolution and design optimal treatment strategies accordingly. To this end, it is crucial to reveal the underlying causes of drug-specific differences in the evolutionary dynamics leading to resistance. However, it remains largely unknown why the rates of resistance evolution via spontaneous mutations and the diversity of mutational paths vary substantially between drugs. Here we comprehensively quantify the distribution of fitness effects (DFE) of mutations, a key determinant of evolutionary dynamics, in the presence of eight antibiotics representing the main modes of action. Using precise high-throughput fitness measurements for genome-wide Escherichia coli gene deletion strains, we find that the width of the DFE varies dramatically between antibiotics and, contrary to conventional wisdom, for some drugs the DFE width is lower than in the absence of stress. We show that this previously underappreciated divergence in DFE width among antibiotics is largely caused by their distinct drug-specific dose-response characteristics. Unlike the DFE, the magnitude of the changes in tolerated drug concentration resulting from genome-wide mutations is similar for most drugs but exceptionally small for the antibiotic nitrofurantoin, i.e., mutations generally have considerably smaller resistance effects for nitrofurantoin than for other drugs. A population genetics model predicts that resistance evolution for drugs with this property is severely limited and confined to reproducible mutational paths. We tested this prediction in laboratory evolution experiments using the “morbidostat”, a device for evolving bacteria in well-controlled drug environments. Nitrofurantoin resistance indeed evolved extremely slowly via reproducible mutations—an almost paradoxical behavior since this drug causes DNA damage and increases the mutation rate. Overall, we identified novel quantitative characteristics of the evolutionary landscape that provide the conceptual foundation for predicting the dynamics of drug resistance evolution.

Crucial role of nonspecific interactions in amyloid nucleation - Šarić, Anđela; Chebaro, Yassmine C.; Knowles, Tuomas P. J.; Frenkel, Daan (Proceedings of the National Academy of Sciences)
Protein oligomers have been implicated as toxic agents in a wide range of amyloid-related diseases. However, it has remained unsolved whether the oligomers are a necessary step in the formation of amyloid fibrils or just a dangerous byproduct. Analogously, it has not been resolved if the amyloid nucleation process is a classical one-step nucleation process or a two-step process involving prenucleation clusters. We use coarse-grained computer simulations to study the effect of nonspecific attractions between peptides on the primary nucleation process underlying amyloid fibrillization. We find that, for peptides that do not attract, the classical one-step nucleation mechanism is possible but only at nonphysiologically high peptide concentrations. At low peptide concentrations, which mimic the physiologically relevant regime, attractive interpeptide interactions are essential for fibril formation. Nucleation then inevitably takes place through a two-step mechanism involving prefibrillar oligomers. We show that oligomers not only help peptides meet each other but also, create an environment that facilitates the conversion of monomers into the β-sheet–rich form characteristic of fibrils. Nucleation typically does not proceed through the most prevalent oligomers but through an oligomer size that is only observed in rare fluctuations, which is why such aggregates might be hard to capture experimentally. Finally, we find that the nucleation of amyloid fibrils cannot be described by classical nucleation theory: in the two-step mechanism, the critical nucleus size increases with increases in both concentration and interpeptide interactions, which is in direct contrast with predictions from classical nucleation theory.
Keywords: multidisciplinary

Anomalous thermomechanical properties of a self-propelled colloidal fluid - Mallory, S. A.; Šarić, Anđela; Valeriani, C.; Cacciuto, A. (Physical Review E)
We use numerical simulations to compute the equation of state of a suspension of spherical self-propelled nanoparticles in two and three dimensions. We study in detail the effect of excluded volume interactions and confinement as a function of the system's temperature, concentration, and strength of the propulsion. We find a striking nonmonotonic dependence of the pressure on the temperature and provide simple scaling arguments to predict and explain the occurrence of such anomalous behavior. We explicitly show how our results have important implications for the effective forces on passive components suspended in a bath of active particles.

Molecular and cellular mechanisms of development underlying congenital diseases - Hashimoto, Masakazu; Morita, Hitoshi; Ueno, Naoto (Congenital Anomalies)
In the last several decades, developmental biology has clarified the molecular mechanisms of embryogenesis and organogenesis. In particular, it has demonstrated that the “tool-kit genes” essential for regulating developmental processes are not only highly conserved among species, but are also used as systems at various times and places in an organism to control distinct developmental events. Therefore, mutations in many of these tool-kit genes may cause congenital diseases involving morphological abnormalities. This link between genes and abnormal morphological phenotypes underscores the importance of understanding how cells behave and contribute to morphogenesis as a result of gene function. Recent improvements in live imaging and in quantitative analyses of cellular dynamics will advance our understanding of the cellular pathogenesis of congenital diseases associated with aberrant morphologies. In these studies, it is critical to select an appropriate model organism for the particular phenomenon of interest.
Keywords: Developmental Biology; Embryology; General Medicine; Pediatrics; Perinatology; and Child Health

Parameterized model checking of token-passing systems - Aminof, Benjamin; Jacobs, Swen; Khalimov, Ayrat; Rubin, Sasha (Verification, Model Checking, and Abstract Interpretation)
We revisit the parameterized model checking problem for token-passing systems and specifications in indexed CTL  ∗ \X. Emerson and Namjoshi (1995, 2003) have shown that parameterized model checking of indexed CTL  ∗ \X in uni-directional token rings can be reduced to checking rings up to some cutoff size. Clarke et al. (2004) have shown a similar result for general topologies and indexed LTL \X, provided processes cannot choose the directions for sending or receiving the token. We unify and substantially extend these results by systematically exploring fragments of indexed CTL  ∗ \X with respect to general topologies. For each fragment we establish whether a cutoff exists, and for some concrete topologies, such as rings, cliques and stars, we infer small cutoffs. Finally, we show that the problem becomes undecidable, and thus no cutoffs exist, if processes are allowed to choose the directions in which they send or from which they receive the token.

Nuclear pores set the speed limit for mitosis - Buchwalter, Abigail; HETZER, Martin W (Cell)
The spindle assembly checkpoint prevents separation of sister chromatids until each kinetochore is attached to the mitotic spindle. Rodriguez-Bravo et al. report that the nuclear pore complex scaffolds spindle assembly checkpoint signaling in interphase, providing a store of inhibitory signals that limits the speed of the subsequent mitosis.
Keywords: General Biochemistry; Genetics and Molecular Biology

Nup50 is required for cell differentiation and exhibits transcription-dependent dynamics - Buchwalter, Abigail L.; Liang, Yun; HETZER, Martin W (Molecular Biology of the Cell)
The nuclear pore complex (NPC) plays a critical role in gene expression by mediating import of transcription regulators into the nucleus and export of RNA transcripts to the cytoplasm. Emerging evidence suggests that in addition to mediating transport, a subset of nucleoporins (Nups) engage in transcriptional activation and elongation at genomic loci that are not associated with NPCs. The underlying mechanism and regulation of Nup mobility on and off nuclear pores remain unclear. Here we show that Nup50 is a mobile Nup with a pronounced presence both at the NPC and in the nucleoplasm that can move between these different localizations. Strikingly, the dynamic behavior of Nup50 in both locations is dependent on active transcription by RNA polymerase II and requires the N-terminal half of the protein, which contains importin α– and Nup153-binding domains. However, Nup50 dynamics are independent of importin α, Nup153, and Nup98, even though the latter two proteins also exhibit transcription-dependent mobility. Of interest, depletion of Nup50 from C2C12 myoblasts does not affect cell proliferation but inhibits differentiation into myotubes. Taken together, our results suggest a transport-independent role for Nup50 in chromatin biology that occurs away from the NPC.
Keywords: Cell Biology; Molecular Biology

Breaching the nuclear envelope in development and disease - Hatch, Emily; HETZER, Martin W (Journal of Cell Biology)
In eukaryotic cells the nuclear genome is enclosed by the nuclear envelope (NE). In metazoans, the NE breaks down in mitosis and it has been assumed that the physical barrier separating nucleoplasm and cytoplasm remains intact during the rest of the cell cycle and cell differentiation. However, recent studies suggest that nonmitotic NE remodeling plays a critical role in development, virus infection, laminopathies, and cancer. Although the mechanisms underlying these NE restructuring events are currently being defined, one common theme is activation of protein kinase C family members in the interphase nucleus to disrupt the nuclear lamina, demonstrating the importance of the lamina in maintaining nuclear integrity.
Keywords: Cell Biology

A 10 deg2 Lyman α survey at z=8.8 with spectroscopic follow-up: Strong constraints on the luminosity function and implications for other surveys - Matthee, Jorryt J; Sobral, David; Swinbank, A. M.; Smail, Ian; Best, P. N.; Kim, Jae-Woo; Franx, Marijn; Milvang-Jensen, Bo; Fynbo, Johan (Monthly Notices of the Royal Astronomical Society)
Candidate galaxies at redshifts of z ∼ 10 are now being found in extremely deep surveys, probing very small areas. As a consequence, candidates are very faint, making spectroscopic confirmation practically impossible. In order to overcome such limitations, we have undertaken the CF-HiZELS survey, which is a large-area, medium-depth near-infrared narrow-band survey targeted at z = 8.8 Lyman α (Lyα) emitters (LAEs) and covering 10 deg2 in part of the SSA22 field with the Canada–France–Hawaii Telescope (CFHT). We surveyed a comoving volume of 4.7 × 106 Mpc3 to a Lyα luminosity limit of 6.3 × 1043舁erg舁s−1. We look for Lyα candidates by applying the following criteria: (i) clear emission-line source, (ii) no optical detections (ugriz from CFHTLS), (iii) no visible detection in the optical stack (ugriz > 27), (iv) visually checked reliable NBJ and J detections and (v) J − K ≤ 0. We compute photometric redshifts and remove a significant amount of dusty lower redshift line-emitters at z ∼ 1.4 or 2.2. A total of 13 Lyα candidates were found, of which two are marked as strong candidates, but the majority have very weak constraints on their spectral energy distributions. Using follow-up observations with SINFONI/VLT, we are able to exclude the most robust candidates as LAEs. We put a strong constraint on the Lyα luminosity function at z ∼ 9 and make realistic predictions for ongoing and future surveys. Our results show that surveys for the highest redshift LAEs are susceptible of multiple contaminations and that spectroscopic follow-up is absolutely necessary.
Keywords: Space and Planetary Science; Astronomy and Astrophysics; galaxies: evolution; galaxies: high-redshift; cosmology: observations; dark ages; reionization; first stars

A relationship between specific star formation rate and metallicity gradient within z ∼ 1 galaxies from KMOS-HiZELS - Stott, John P.; Sobral, David; Swinbank, A. M.; Smail, Ian; Bower, Richard; Best, Philip N.; Sharples, Ray M.; Geach, James E.; Matthee, Jorryt J (Monthly Notices of the Royal Astronomical Society)
We have observed a sample of typical z ∼ 1 star-forming galaxies, selected from the HiZELS survey, with the new K-band Multi-Object Spectrograph (KMOS) near-infrared, multi-integral field unit instrument on the Very Large Telescope (VLT), in order to obtain their dynamics and metallicity gradients. The majority of our galaxies have a metallicity gradient consistent with being flat or negative (i.e. higher metallicity cores than outskirts). Intriguingly, we find a trend between metallicity gradient and specific star formation rate (sSFR), such that galaxies with a high sSFR tend to have relatively metal poor centres, a result which is strengthened when combined with data sets from the literature. This result appears to explain the discrepancies reported between different high-redshift studies and varying claims for evolution. From a galaxy evolution perspective, the trend we see would mean that a galaxy's sSFR is governed by the amount of metal-poor gas that can be funnelled into its core, triggered either by merging or through efficient accretion. In fact, merging may play a significant role as it is the starburst galaxies at all epochs, which have the more positive metallicity gradients. Our results may help to explain the origin of the fundamental metallicity relation, in which galaxies at a fixed mass are observed to have lower metallicities at higher star formation rates, especially if the metallicity is measured in an aperture encompassing only the central regions of the galaxy. Finally, we note that this study demonstrates the power of KMOS as an efficient instrument for large-scale resolved galaxy surveys.
Keywords: Space and Planetary Science; Astronomy and Astrophysics; galaxies: abundances; galaxies: evolution; galaxies: kinematics and dynamics

Online bipartite matching with decomposable weights - Charikar, Moses; Henzinger, Monika H; Nguyễn, Huy L. (22nd Annual European Symposium on Algorithms)
We study a weighted online bipartite matching problem: G(V 1, V 2, E) is a weighted bipartite graph where V 1 is known beforehand and the vertices of V 2 arrive online. The goal is to match vertices of V 2 as they arrive to vertices in V 1, so as to maximize the sum of weights of edges in the matching. If assignments to V 1 cannot be changed, no bounded competitive ratio is achievable. We study the weighted online matching problem with free disposal, where vertices in V 1 can be assigned multiple times, but only get credit for the maximum weight edge assigned to them over the course of the algorithm. For this problem, the greedy algorithm is 0.5-competitive and determining whether a better competitive ratio is achievable is a well known open problem. We identify an interesting special case where the edge weights are decomposable as the product of two factors, one corresponding to each end point of the edge. This is analogous to the well studied related machines model in the scheduling literature, although the objective functions are different. For this case of decomposable edge weights, we design a 0.5664 competitive randomized algorithm in complete bipartite graphs. We show that such instances with decomposable weights are non-trivial by establishing upper bounds of 0.618 for deterministic and 0.8 for randomized algorithms. A tight competitive ratio of 1 − 1/e ≈ 0.632 was known previously for both the 0-1 case as well as the case where edge weights depend on the offline vertices only, but for these cases, reassignments cannot change the quality of the solution. Beating 0.5 for weighted matching where reassignments are necessary has been a significant challenge. We thus give the first online algorithm with competitive ratio strictly better than 0.5 for a non-trivial case of weighted matching with free disposal.

Decremental single-source shortest paths on undirected graphs in near-linear total update time - Henzinger, Monika H; Krinninger, Sebastian; Nanongkai, Danupon (55th Annual Symposium on Foundations of Computer Science)
The decremental single-source shortest paths (SSSP) problem concerns maintaining the distances between a given source node s to every node in an n-node m-edge graph G undergoing edge deletions. While its static counterpart can be easily solved in near-linear time, this decremental problem is much more challenging even in the undirected unweighted case. In this case, the classic O(mn) total update time of Even and Shiloach (JACM 1981) has been the fastest known algorithm for three decades. With the loss of a (1 + ε)-approximation factor, the running time was recently improved to O(n 2+o(1) ) by Bernstein and Roditty (SODA 2011), and more recently to O(n 1.8+o(1) + m 1+o(1) ) by Henzinger, Krinninger, and Nanongkai (SODA 2014). In this paper, we finally bring the running time of this case down to near-linear: We give a (1 + ε)-approximation algorithm with O(m 1+o(1) ) total update time, thus obtaining near-linear time. Moreover, we obtain O(m 1+o(1) log W) time for the weighted case, where the edge weights are integers from 1 to W. The only prior work on weighted graphs in o(mn log W) time is the O(mn 0.986 log W)-time algorithm by Henzinger, Krinninger, and Nanongkai (STOC 2014) which works for the general weighted directed case. In contrast to the previous results which rely on maintaining a sparse emulator, our algorithm relies on maintaining a so-called sparse (d, ε)-hop set introduced by Cohen (JACM 2000) in the PRAM literature. A (d, ε)-hop set of a graph G = (V, E) is a set E' of weighted edges such that the distance between any pair of nodes in G can be (1 + ε)-approximated by their d-hop distance (given by a path containing at most d edges) on G'=(V, E∪E'). Our algorithm can maintain an (n o(1) , ε)-hop set of near-linear size in near-linear time under edge deletions. It is the first of its kind to the best of our knowledge. To maintain the distances on this hop set, we develop a monotone bounded-hop Even-Shiloach tree. It results from extending and combining the monotone Even-Shiloach tree of Henzinger, Krinninger, and Nanongkai (FOCS 2013) with the bounded-hop SSSP technique of Bernstein (STOC 2013). These two new tools might be of independent interest.

Sublinear-time decremental algorithms for single-source reachability and shortest paths on directed graphs - Henzinger, Monika H; Krinninger, Sebastian; Nanongkai, Danupon (46th Annual ACM Symposium on Theory of Computing)
We consider dynamic algorithms for maintaining Single-Source Reachability (SSR) and approximate Single-Source Shortest Paths (SSSP) on n-node m-edge directed graphs under edge deletions (decremental algorithms). The previous fastest algorithm for SSR and SSSP goes back three decades to Even and Shiloach (JACM 1981); it has O(1) query time and O(mn) total update time (i.e., linear amortized update time if all edges are deleted). This algorithm serves as a building block for several other dynamic algorithms. The question whether its total update time can be improved is a major, long standing, open problem. In this paper, we answer this question affirmatively. We obtain a randomized algorithm which, in a simplified form, achieves an Õ(mn0.984) expected total update time for SSR and (1 + ε)-approximate SSSP, where Õ(·) hides poly log n. We also extend our algorithm to achieve roughly the same running time for Strongly Connected Components (SCC), improving the algorithm of Roditty and Zwick (FOCS 2002), and an algorithm that improves the Õ (mn log W)-time algorithm of Bernstein (STOC 2013) for approximating SSSP on weighted directed graphs, where the edge weights are integers from 1 to W. All our algorithms have constant query time in the worst case.

A subquadratic-time algorithm for decremental single-source shortest paths - Henzinger, Monika H; Krinninger, Sebastian; Nanongkai, Danupon (25th Annual ACM-SIAM Symposium on Discrete Algorithms)
We study dynamic (1 + ∊)-approximation algorithms for the single-source shortest paths problem in an unweighted undirected n-node m-edge graph under edge deletions. The fastest algorithm for this problem is an algorithm with O(n2+o(1)) total update time and constant query time by Bernstein and Roditty (SODA 2011). In this paper, we improve the total update time to O(n1.8+o(1) + m1+o(1)) while keeping the query time constant. This running time is essentially tight when m = Ω(n1.8) since we need Ω(m) time even in the static setting. For smaller values of m, the running time of our algorithm is subquadratic, and is the first that breaks through the quadratic time barrier. In obtaining this result, we develop a fast algorithm for what we call center cover data structure. We also make non-trivial extensions to our previous techniques called lazy-update and monotone Even-Shiloach trees (ICALP 2013 and FOCS 2013). As by-products of our new techniques, we obtain two new results for the decremental all-pairs shortest-paths problem. Our first result is the first approximation algorithm whose total update time is faster than Õ(mn) for all values of m. Our second result is a new trade-off between the total update time and the additive approximation guarantee.

Deterministic fully dynamic data structures for vertex cover and matching - Bhattacharya, Sayan; Henzinger, Monika H; Italiano, Giuseppe F. (26th Annual ACM-SIAM Symposium on Discrete Algorithms)
We present the first deterministic data structures for maintaining approximate minimum vertex cover and maximum matching in a fully dynamic graph in time per update. In particular, for minimum vertex cover we provide deterministic data structures for maintaining a (2 + ε) approximation in O(log n/ε2) amortized time per update. For maximum matching, we show how to maintain a (3 + e) approximation in O(m1/3/ε2) amortized time per update, and a (4 + ε) approximation in O(m1/3/ε2) worst-case time per update. Our data structure for fully dynamic minimum vertex cover is essentially near-optimal and settles an open problem by Onak and Rubinfeld [13].

Size-dependent same-material tribocharging in insulating grains - Waitukaitis, Scott R; Lee, Victor; Pierson, James; Forman, Steven; Jaeger, Heinrich (APS Physics, Physical Review Letters)
Observations of flowing granular matter have suggested that same-material tribocharging depends on particle size, typically rendering large grains positive and small ones negative. Models assuming the transfer of trapped electrons can account for this trend, but have not been validated. Tracking individual grains in an electric field, we show quantitatively that charge is transferred based on size between materially identical grains. However, the surface density of trapped electrons, measured independently by thermoluminescence techniques, is orders of magnitude too small to account for the scale of charge transferred. This reveals that trapped electrons are not a necessary ingredient for same-material tribocharging.

Regulation of gene expression through a transcriptional repressor that senses acyl-chain length in membrane phospholipids - Hofbauer, Harald F.; Schopf, Florian H.; Schleifer, Hannes; Knittelfelder, Oskar L.; Pieber, Bartholomäus; Rechberger, Gerald N.; Wolinski, Heimo; Gaspar, Maria L.; Kappe, C. Oliver; Stadlmann, Johannes; Mechtler, Karl; Zenz, Alexandra; et al. (Developmental Cell)
Membrane phospholipids typically contain fatty acids (FAs) of 16 and 18 carbon atoms. This particular chain length is evolutionarily highly conserved and presumably provides maximum stability and dynamic properties to biological membranes in response to nutritional or environmental cues. Here, we show that the relative proportion of C16 versus C18 FAs is regulated by the activity of acetyl-CoA carboxylase (Acc1), the first and rate-limiting enzyme of FA de novo synthesis. Acc1 activity is attenuated by AMPK/Snf1-dependent phosphorylation, which is required to maintain an appropriate acyl-chain length distribution. Moreover, we find that the transcriptional repressor Opi1 preferentially binds to C16 over C18 phosphatidic acid (PA) species: thus, C16-chain containing PA sequesters Opi1 more effectively to the ER, enabling AMPK/Snf1 control of PA acyl-chain length to determine the degree of derepression of Opi1 target genes. These findings reveal an unexpected regulatory link between the major energy-sensing kinase, membrane lipid composition, and transcription.

Approximating the minimum cycle mean - Chatterjee, Krishnendu; Henzinger, Monika H; Krinninger, Sebastian; Loitzenbauer, Veronika; Raskin, Michael (Theoretical Computer Science)
We consider directed graphs where each edge is labeled with an integer weight and study the fundamental algorithmic question of computing the value of a cycle with minimum mean weight. Our contributions are twofold: (1) First we show that the algorithmic question is reducible to the problem of a logarithmic number of min-plus matrix multiplications of n×n-matrices, where n is the number of vertices of the graph. (2) Second, when the weights are nonnegative, we present the first (1+ε)-approximation algorithm for the problem and the running time of our algorithm is Õ(nωlog3(nW/ε)/ε),1 where O(nω) is the time required for the classic n×n-matrix multiplication and W is the maximum value of the weights. With an additional O(log(nW/ε)) factor in space a cycle with approximately optimal weight can be computed within the same time bound.

A logic-based framework for verifying consensus algorithms - Dragoi, Cezara; Henzinger, Thomas A; Veith, Helmut; Widder, Josef; Zufferey, Damien
Fault-tolerant distributed algorithms play an important role in ensuring the reliability of many software applications. In this paper we consider distributed algorithms whose computations are organized in rounds. To verify the correctness of such algorithms, we reason about (i) properties (such as invariants) of the state, (ii) the transitions controlled by the algorithm, and (iii) the communication graph. We introduce a logic that addresses these points, and contains set comprehensions with cardinality constraints, function symbols to describe the local states of each process, and a limited form of quantifier alternation to express the verification conditions. We show its use in automating the verification of consensus algorithms. In particular, we give a semi-decision procedure for the unsatisfiability problem of the logic and identify a decidable fragment. We successfully applied our framework to verify the correctness of a variety of consensus algorithms tolerant to both benign faults (message loss, process crashes) and value faults (message corruption).

Probabilistic programming - Gordon, Andrew; Henzinger, Thomas A; Nori, Aditya; Rajamani, Sriram (Proceedings of the on Future of Software Engineering)
Probabilistic programs are usual functional or imperative programs with two added constructs: (1) the ability to draw values at random from distributions, and (2) the ability to condition values of variables in a program via observations. Models from diverse application areas such as computer vision, coding theory, cryptographic protocols, biology and reliability analysis can be written as probabilistic programs. Probabilistic inference is the problem of computing an explicit representation of the probability distribution implicitly specified by a probabilistic program. Depending on the application, the desired output from inference may vary-we may want to estimate the expected value of some function f with respect to the distribution, or the mode of the distribution, or simply a set of samples drawn from the distribution. In this paper, we describe connections this research area called \Probabilistic Programming" has with programming languages and software engineering, and this includes language design, and the static and dynamic analysis of programs. We survey current state of the art and speculate on promising directions for future research.

On the BCS gap equation for superfluid fermionic gases - Bräunlich, Gerhard; Hainzl, Christian; Seiringer, Robert (Proceedings of the QMath12 Conference)
We present a rigorous derivation of the BCS gap equation for superfluid fermionic gases with point interactions. Our starting point is the BCS energy functional, whose minimizer we investigate in the limit when the range of the interaction potential goes to zero.

Edit propagation using geometric relationship functions - Guerrero, Paul; Jeschke, Stefan; Wimmer, Michael; Wonka, Peter (ACM Transactions on Graphics)
We propose a method for propagating edit operations in 2D vector graphics, based on geometric relationship functions. These functions quantify the geometric relationship of a point to a polygon, such as the distance to the boundary or the direction to the closest corner vertex. The level sets of the relationship functions describe points with the same relationship to a polygon. For a given query point, we first determine a set of relationships to local features, construct all level sets for these relationships, and accumulate them. The maxima of the resulting distribution are points with similar geometric relationships. We show extensions to handle mirror symmetries, and discuss the use of relationship functions as local coordinate systems. Our method can be applied, for example, to interactive floorplan editing, and it is especially useful for large layouts, where individual edits would be cumbersome. We demonstrate populating 2D layouts with tens to hundreds of objects by propagating relatively few edit operations.

Constrained Verifiable Random Functions - Fuchsbauer, Georg (SCN 2014)
We extend the notion of verifiable random functions (VRF) to constrained VRFs, which generalize the concept of constrained pseudorandom functions, put forward by Boneh and Waters (Asiacrypt’13), and independently by Kiayias et al. (CCS’13) and Boyle et al. (PKC’14), who call them delegatable PRFs and functional PRFs, respectively. In a standard VRF the secret key sk allows one to evaluate a pseudorandom function at any point of its domain; in addition, it enables computation of a non-interactive proof that the function value was computed correctly. In a constrained VRF from the key sk one can derive constrained keys skS for subsets S of the domain, which allow computation of function values and proofs only at points in S. After formally defining constrained VRFs, we derive instantiations from the multilinear-maps-based constrained PRFs by Boneh and Waters, yielding a VRF with constrained keys for any set that can be decided by a polynomial-size circuit. Our VRFs have the same function values as the Boneh-Waters PRFs and are proved secure under the same hardness assumption, showing that verifiability comes at no cost. Constrained (functional) VRFs were stated as an open problem by Boyle et al.

Generalised interpolation by solving recursion free-horn clauses - Gupta, Ashutosh; Popeea, Corneliu; Rybalchenko, Andrey (Electronic Proceedings in Theoretical Computer Science, EPTCS)
In this paper we present INTERHORN, a solver for recursion-free Horn clauses. The main application domain of INTERHORN lies in solving interpolation problems arising in software verification. We show how a range of interpolation problems, including path, transition, nested, state/transition and well-founded interpolation can be handled directly by INTERHORN. By detailing these interpolation problems and their Horn clause representations, we hope to encourage the emergence of a common back-end interpolation interface useful for diverse verification tools.

PtSi clustering in silicon probed by transport spectroscopy - Mongillo, Massimo; Spathis, Panayotis N; Georgios Katsaros; De Franceschi, Silvano; Gentile, Pascal; Rurali, Riccardo; Cartoixà, Xavier (Physical Review X)
Metal silicides formed by means of thermal annealing processes are employed as contact materials in microelectronics. Control of the structure of silicide/silicon interfaces becomes a critical issue when the characteristic size of the device is reduced below a few tens of nanometers. Here, we report on silicide clustering occurring within the channel of PtSi/Si/PtSi Schottky-barrier transistors. This phenomenon is investigated through atomistic simulations and low-temperature resonant-tunneling spectroscopy. Our results provide evidence for the segregation of a PtSi cluster with a diameter of a few nanometers from the silicide contact. The cluster acts as a metallic quantum dot giving rise to distinct signatures of quantum transport through its discrete energy states.

Topology-preserving watermarking of vector graphics - Huber, Stefan; Held, Martin; Meerwald, Peter; Kwitt, Roland (International Journal of Computational Geometry and Applications)
Watermarking techniques for vector graphics dislocate vertices in order to embed imperceptible, yet detectable, statistical features into the input data. The embedding process may result in a change of the topology of the input data, e.g., by introducing self-intersections, which is undesirable or even disastrous for many applications. In this paper we present a watermarking framework for two-dimensional vector graphics that employs conventional watermarking techniques but still provides the guarantee that the topology of the input data is preserved. The geometric part of this framework computes so-called maximum perturbation regions (MPR) of vertices. We propose two efficient algorithms to compute MPRs based on Voronoi diagrams and constrained triangulations. Furthermore, we present two algorithms to conditionally correct the watermarked data in order to increase the watermark embedding capacity and still guarantee topological correctness. While we focus on the watermarking of input formed by straight-line segments, one of our approaches can also be extended to circular arcs. We conclude the paper by demonstrating and analyzing the applicability of our framework in conjunction with two well-known watermarking techniques.

Bose gases, Bose-Einstein condensation, and the Bogoliubov approximation - Seiringer, Robert (Journal of Mathematical Physics)
We review recent progress towards a rigorous understanding of the Bogoliubov approximation for bosonic quantum many-body systems. We focus, in particular, on the excitation spectrum of a Bose gas in the mean-field (Hartree) limit. A list of open problems will be discussed at the end.

Mutational studies on resurrected ancestral proteins reveal conservation of site-specific amino acid preferences throughout evolutionary history - Risso, Valeria; Manssour Triedo, Fadia; Delgado Delgado, Asuncion; Arco, Rocio; Barroso Deljesús, Alicia; Inglés Prieto, Álvaro; Godoy Ruiz, Raquel; Gavira, Josè; Gaucher, Eric; Ibarra Molero, Beatriz; Sánchez Ruiz, Jose (Molecular Biology and Evolution)
Local protein interactions ("molecular context" effects) dictate amino acid replacements and can be described in terms of site-specific, energetic preferences for any different amino acid. It has been recently debated whether these preferences remain approximately constant during evolution or whether, due to coevolution of sites, they change strongly. Such research highlights an unresolved and fundamental issue with far-reaching implications for phylogenetic analysis and molecular evolution modeling. Here, we take advantage of the recent availability of phenotypically supported laboratory resurrections of Precambrian thioredoxins and β-lactamases to experimentally address the change of site-specific amino acid preferences over long geological timescales. Extensive mutational analyses support the notion that evolutionary adjustment to a new amino acid may occur, but to a large extent this is insufficient to erase the primitive preference for amino acid replacements. Generally, site-specific amino acid preferences appear to remain conserved throughout evolutionary history despite local sequence divergence. We show such preference conservation to be readily understandable in molecular terms and we provide crystallographic evidence for an intriguing structural-switch mechanism: Energetic preference for an ancestral amino acid in a modern protein can be linked to reorganization upon mutation to the ancestral local structure around the mutated site. Finally, we point out that site-specific preference conservation naturally leads to one plausible evolutionary explanation for the existence of intragenic global suppressor mutations.

On the geometric ramsey number of outerplanar graphs - Cibulka, Josef; Gao, Pu; Krcál, Marek; Valla, Tomáš; Valtr, Pavel (Discrete & Computational Geometry)
We prove polynomial upper bounds of geometric Ramsey numbers of pathwidth-2 outerplanar triangulations in both convex and general cases. We also prove that the geometric Ramsey numbers of the ladder graph on 2n vertices are bounded by O(n3) and O(n10), in the convex and general case, respectively. We then apply similar methods to prove an (Formula presented.) upper bound on the Ramsey number of a path with n ordered vertices.

Partial shape matching using transformation parameter similarity - Guerrero, Paul; Auzinger, Thomas; Wimmer, Michael; Jeschke, Stefan (Computer Graphics Forum)
In this paper, we present a method for non-rigid, partial shape matching in vector graphics. Given a user-specified query region in a 2D shape, similar regions are found, even if they are non-linearly distorted. Furthermore, a non-linear mapping is established between the query regions and these matches, which allows the automatic transfer of editing operations such as texturing. This is achieved by a two-step approach. First, pointwise correspondences between the query region and the whole shape are established. The transformation parameters of these correspondences are registered in an appropriate transformation space. For transformations between similar regions, these parameters form surfaces in transformation space, which are extracted in the second step of our method. The extracted regions may be related to the query region by a non-rigid transform, enabling non-rigid shape matching. In this paper, we present a method for non-rigid, partial shape matching in vector graphics. Given a user-specified query region in a 2D shape, similar regions are found, even if they are non-linearly distorted. Furthermore, a non-linear mapping is established between the query regions and these matches, which allows the automatic transfer of editing operations such as texturing. This is achieved by a two-step approach. First, pointwise correspondences between the query region and the whole shape are established. The transformation parameters of these correspondences are registered in an appropriate transformation space. For transformations between similar regions, these parameters form surfaces in transformation space, which are extracted in the second step of our method. The extracted regions may be related to the query region by a non-rigid transform, enabling non-rigid shape matching.

An auxin-mediated shift toward growth isotropy promotes organ formation at the shoot meristem in Arabidopsis - Sassi, Massimiliano; Ali, Olivier; Boudon, Frédéric; Cloarec, Gladys; Abad, Ursula; Cellier, Coralie; Chen, Xu; Gilles, Benjamin; Milani, Pascale; Friml, Jirí; Vernoux, Teva; Godin, Christophe; et al. (Current Biology)
To control morphogenesis, molecular regulatory networks have to interfere with the mechanical properties of the individual cells of developing organs and tissues, but how this is achieved is not well known. We study this issue here in the shoot meristem of higher plants, a group of undifferentiated cells where complex changes in growth rates and directions lead to the continuous formation of new organs [1, 2]. Here, we show that the plant hormone auxin plays an important role in this process via a dual, local effect on the extracellular matrix, the cell wall, which determines cell shape. Our study reveals that auxin not only causes a limited reduction in wall stiffness but also directly interferes with wall anisotropy via the regulation of cortical microtubule dynamics. We further show that to induce growth isotropy and organ outgrowth, auxin somehow interferes with the cortical microtubule-ordering activity of a network of proteins, including AUXIN BINDING PROTEIN 1 and KATANIN 1. Numerical simulations further indicate that the induced isotropy is sufficient to amplify the effects of the relatively minor changes in wall stiffness to promote organogenesis and the establishment of new growth axes in a robust manner.

Inhibition of cell expansion by rapid ABP1-mediated auxin effect on microtubules - Chen, Xu; Grandont, Laurie; Li, Hongjiang; Hauschild, Robert; Paque, Sébastien; Abuzeineh, Anas; Rakusova, Hana; Benková, Eva; Perrot Rechenmann, Catherine; Friml, Jirí (Nature)
The prominent and evolutionarily ancient role of the plant hormone auxin is the regulation of cell expansion. Cell expansion requires ordered arrangement of the cytoskeleton but molecular mechanisms underlying its regulation by signalling molecules including auxin are unknown. Here we show in the model plant Arabidopsis thaliana that in elongating cells exogenous application of auxin or redistribution of endogenous auxin induces very rapid microtubule re-orientation from transverse to longitudinal, coherent with the inhibition of cell expansion. This fast auxin effect requires auxin binding protein 1 (ABP1) and involves a contribution of downstream signalling components such as ROP6 GTPase, ROP-interactive protein RIC1 and the microtubule-severing protein katanin. These components are required for rapid auxin-and ABP1-mediated re-orientation of microtubules to regulate cell elongation in roots and dark-grown hypocotyls as well as asymmetric growth during gravitropic responses.

Extensional crisis and proving identity - Gupta, Ashutosh; Kovács, Laura; Kragl, Bernhard; Voronkov, Andrei (ATVA 2014)
Extensionality axioms are common when reasoning about data collections, such as arrays and functions in program analysis, or sets in mathematics. An extensionality axiom asserts that two collections are equal if they consist of the same elements at the same indices. Using extensionality is often required to show that two collections are equal. A typical example is the set theory theorem (∀x)(∀y)x∪y = y ∪x. Interestingly, while humans have no problem with proving such set identities using extensionality, they are very hard for superposition theorem provers because of the calculi they use. In this paper we show how addition of a new inference rule, called extensionality resolution, allows first-order theorem provers to easily solve problems no modern first-order theorem prover can solve. We illustrate this by running the VAMPIRE theorem prover with extensionality resolution on a number of set theory and array problems. Extensionality resolution helps VAMPIRE to solve problems from the TPTP library of first-order problems that were never solved before by any prover.

Lipschitz robustness of finite-state transducers - Henzinger, Thomas A; Otop, Jan; Samanta, Roopsha (Leibniz International Proceedings in Informatics, LIPIcs)
We investigate the problem of checking if a finite-state transducer is robust to uncertainty in its input. Our notion of robustness is based on the analytic notion of Lipschitz continuity - a transducer is K-(Lipschitz) robust if the perturbation in its output is at most K times the perturbation in its input. We quantify input and output perturbation using similarity functions. We show that K-robustness is undecidable even for deterministic transducers. We identify a class of functional transducers, which admits a polynomial time automata-theoretic decision procedure for K-robustness. This class includes Mealy machines and functional letter-to-letter transducers. We also study K-robustness of nondeterministic transducers. Since a nondeterministic transducer generates a set of output words for each input word, we quantify output perturbation using setsimilarity functions. We show that K-robustness of nondeterministic transducers is undecidable, even for letter-to-letter transducers. We identify a class of set-similarity functions which admit decidable K-robustness of letter-to-letter transducers.

Cost-aware automatic program repair - Samanta, Roopsha; Olivo, Oswaldo; Allen, Emerson
We present a formal framework for repairing infinite-state, imperative, sequential programs, with (possibly recursive) procedures and multiple assertions; the framework can generate repaired programs by modifying the original erroneous program in multiple program locations, and can ensure the readability of the repaired program using user-defined expression templates; the framework also generates a set of inductive assertions that serve as a proof of correctness of the repaired program. As a step toward integrating programmer intent and intuition in automated program repair, we present a cost-aware formulation - given a cost function associated with permissible statement modifications, the goal is to ensure that the total program modification cost does not exceed a given repair budget. As part of our predicate abstractionbased solution framework, we present a sound and complete algorithm for repair of Boolean programs. We have developed a prototype tool based on SMT solving and used it successfully to repair diverse errors in benchmark C programs.

Functionals on triangulations of delaunay sets - Dolbilin, Nikolai; Edelsbrunner, Herbert; Glazyrin, Alexey; Musin, Oleg (Moscow Mathematical Journal)
We study densities of functionals over uniformly bounded triangulations of a Delaunay set of vertices, and prove that the minimum is attained for the Delaunay triangulation if this is the case for finite sets.

Variance predicts salience in central sensory processing - Hermundstad, Ann; Briguglio, John; Conte, Mary; Victor, Jonathan; Balasubramanian, Vijay; Tkacik, Gasper (eLife)
Information processing in the sensory periphery is shaped by natural stimulus statistics. In the periphery, a transmission bottleneck constrains performance; thus efficient coding implies that natural signal components with a predictably wider range should be compressed. In a different regime—when sampling limitations constrain performance—efficient coding implies that more resources should be allocated to informative features that are more variable. We propose that this regime is relevant for sensory cortex when it extracts complex features from limited numbers of sensory samples. To test this prediction, we use central visual processing as a model: we show that visual sensitivity for local multi-point spatial correlations, described by dozens of independently-measured parameters, can be quantitatively predicted from the structure of natural images. This suggests that efficient coding applies centrally, where it extends to higher-order sensory features and operates in a regime in which sensitivity increases with feature variability.

Sequential effects in continued visual search: Using fixation-related potentials to compare distractor processing before and after target detection - Körner, Christof; Braunstein, Verena; Stangl, Matthias; Schlögl, Alois; Neuper, Christa; Ischebeck, Anja (Psychophysiology)
To search for a target in a complex environment is an everyday behavior that ends with finding the target. When we search for two identical targets, however, we must continue the search after finding the first target and memorize its location. We used fixation-related potentials to investigate the neural correlates of different stages of the search, that is, before and after finding the first target. Having found the first target influenced subsequent distractor processing. Compared to distractor fixations before the first target fixation, a negative shift was observed for three subsequent distractor fixations. These results suggest that processing a target in continued search modulates the brain's response, either transiently by reflecting temporary working memory processes or permanently by reflecting working memory retention.

Y-linked Mendelian inheritance of giant and dwarf male morphs in shell-brooding cichlids - Ocana, Sabine; Meidl, Patrick; Bonfils, Danielle; Taborsky, Michael (Proceedings of the Royal Society of London Series B Biological Sciences)
Behavioural variation among conspecifics is typically contingent on individual state or environmental conditions. Sex-specific genetic polymorphisms are enigmatic because they lack conditionality, and genes causing adaptive trait variation in one sex may reduce Darwinian fitness in the other. One way to avoid such genetic antagonism is to control sex-specific traits by inheritance via sex chromosomes. Here, controlled laboratory crossings suggest that in snail-brooding cichlid fish a single locus, two-allele polymorphism located on a sex-linked chromosome of heterogametic males generates an extreme reproductive dimorphism. Both natural and sexual selection are responsible for exceptionally large body size of bourgeois males, creating a niche for a miniature male phenotype to evolve. This extreme intrasexual dimorphism results from selection on opposite size thresholds caused by a single ecological factor, empty snail shells used as breeding substrate. Paternity analyses reveal that in the field parasitic dwarf males sire the majority of offspring in direct sperm competition with large nest owners exceeding their size more than 40 times. Apparently, use of empty snail shells as breeding substrate and single locus sex-linked inheritance of growth are the major ecological and genetic mechanisms responsible for the extreme intrasexual diversity observed in Lamprologus callipterus.

Translation-invariant quasi-free states for fermionic systems and the BCS approximation - Bräunlich, Gerhard; Hainzl, Christian; Seiringer, Robert (Reviews in Mathematical Physics)
We study translation-invariant quasi-free states for a system of fermions with two-particle interactions. The associated energy functional is similar to the BCS functional but also includes direct and exchange energies. We show that for suitable short-range interactions, these latter terms only lead to a renormalization of the chemical potential, with the usual properties of the BCS functional left unchanged. Our analysis thus represents a rigorous justification of part of the BCS approximation. We give bounds on the critical temperature below which the system displays superfluidity.

Functional and bioinformatics analysis of two Campylobacter jejuni homologs of the thiol-disulfide oxidoreductase, DsbA - Grabowska, Anna; Wywiał, Ewa; Dunin Horkawicz, Stanislaw; Łasica, Anna; Wösten, Marc; Nagy-Staron, Anna A; Godlewska, Renata; Bocian Ostrzycka, Katarzyna; Pieńkowska, Katarzyna; Łaniewski, Paweł; Bujnicki, Janusz; Van Putten, Jos; et al. (PLoS One)
Background: Bacterial Dsb enzymes are involved in the oxidative folding of many proteins, through the formation of disulfide bonds between their cysteine residues. The Dsb protein network has been well characterized in cells of the model microorganism Escherichia coli. To gain insight into the functioning of the Dsb system in epsilon-Proteobacteria, where it plays an important role in the colonization process, we studied two homologs of the main Escherichia coli Dsb oxidase (EcDsbA) that are present in the cells of the enteric pathogen Campylobacter jejuni, the most frequently reported bacterial cause of human enteritis in the world. Methods and Results: Phylogenetic analysis suggests the horizontal transfer of the epsilon-Proteobacterial DsbAs from a common ancestor to gamma-Proteobacteria, which then gave rise to the DsbL lineage. Phenotype and enzymatic assays suggest that the two C. jejuni DsbAs play different roles in bacterial cells and have divergent substrate spectra. CjDsbA1 is essential for the motility and autoagglutination phenotypes, while CjDsbA2 has no impact on those processes. CjDsbA1 plays a critical role in the oxidative folding that ensures the activity of alkaline phosphatase CjPhoX, whereas CjDsbA2 is crucial for the activity of arylsulfotransferase CjAstA, encoded within the dsbA2-dsbB-astA operon. Conclusions: Our results show that CjDsbA1 is the primary thiol-oxidoreductase affecting life processes associated with bacterial spread and host colonization, as well as ensuring the oxidative folding of particular protein substrates. In contrast, CjDsbA2 activity does not affect the same processes and so far its oxidative folding activity has been demonstrated for one substrate, arylsulfotransferase CjAstA. The results suggest the cooperation between CjDsbA2 and CjDsbB. In the case of the CjDsbA1, this cooperation is not exclusive and there is probably another protein to be identified in C. jejuni cells that acts to re-oxidize CjDsbA1. Altogether the data presented here constitute the considerable insight to the Epsilonproteobacterial Dsb systems, which have been poorly understood so far.

Functional deficiency of MHC class i enhances LTP and abolishes LTD in the nucleus accumbens of mice - Edamura, Mitsuhiro; Murakami, Gen; Meng, Hongrui; Itakura, Makoto; Shigemoto, Ryuichi; Fukuda, Atsuo; Nakahara, Daiichiro (PLoS One)
Major histocompatibility complex class I (MHCI) molecules were recently identified as novel regulators of synaptic plasticity. These molecules are expressed in various brain areas, especially in regions undergoing activity-dependent synaptic plasticity, but their role in the nucleus accumbens (NAc) is unknown. In this study, we investigated the effects of genetic disruption of MHCI function, through deletion of β2-microblobulin, which causes lack of cell surface expression of MHCI. First, we confirmed that MHCI molecules are expressed in the NAc core in wild-type mice. Second, we performed electrophysiological recordings with NAc core slices from wild-type and β2-microglobulin knock-out mice lacking cell surface expression of MHCI. We found that low frequency stimulation induced long-term depression in wild-type but not knock-out mice, whereas high frequency stimulation induced long-term potentiation in both genotypes, with a larger magnitude in knock-out mice. Furthermore, we demonstrated that knock-out mice showed more persistent behavioral sensitization to cocaine, which is a NAc-related behavior. Using this model, we analyzed the density of total AMPA receptors and their subunits GluR1 and GluR2 in the NAc core, by SDS-digested freeze-fracture replica labeling. After repeated cocaine exposure, the density of GluR1 was increased, but there was no change in total AMPA receptors and GluR2 levels in wildtype mice. In contrast, following repeated cocaine exposure, increased densities of total AMPA receptors, GluR1 and GluR2 were observed in knock-out mice. These results indicate that functional deficiency of MHCI enhances synaptic potentiation, induced by electrical and pharmacological stimulation.

SAC phosphoinositide phosphatases at the tonoplast mediate vacuolar function in Arabidopsis - Nováková, Petra; Hirsch, Sibylle; Feraru, Elena; Tejos, Ricardo; Van Wijk, Ringo; Viaene, Tom; Heilmann, Mareike; Lerche, Jennifer; De Rycke, Riet; Feraru, Mugurel; Grones, Peter; Van Montagu, Marc; et al. (PNAS)
Phosphatidylinositol (PtdIns) is a structural phospholipid that can be phosphorylated into various lipid signaling molecules, designated polyphosphoinositides (PPIs). The reversible phosphorylation of PPIs on the 3, 4, or 5 position of inositol is performed by a set of organelle-specific kinases and phosphatases, and the characteristic head groups make these molecules ideal for regulating biological processes in time and space. In yeast and mammals, PtdIns3P and PtdIns(3,5)P2 play crucial roles in trafficking toward the lytic compartments, whereas the role in plants is not yet fully understood. Here we identified the role of a land plant-specific subgroup of PPI phosphatases, the suppressor of actin 2 (SAC2) to SAC5, during vacuolar trafficking and morphogenesis in Arabidopsis thaliana. SAC2-SAC5 localize to the tonoplast along with PtdIns3P, the presumable product of their activity. In SAC gain- and loss-of-function mutants, the levels of PtdIns monophosphates and bisphosphates were changed, with opposite effects on the morphology of storage and lytic vacuoles, and the trafficking toward the vacuoles was defective. Moreover, multiple sac knockout mutants had an increased number of smaller storage and lytic vacuoles, whereas extralarge vacuoles were observed in the overexpression lines, correlating with various growth and developmental defects. The fragmented vacuolar phenotype of sac mutants could be mimicked by treating wild-type seedlings with PtdIns(3,5)P2, corroborating that this PPI is important for vacuole morphology. Taken together, these results provide evidence that PPIs, together with their metabolic enzymes SAC2-SAC5, are crucial for vacuolar trafficking and for vacuolar morphology and function in plants.

Mathematical model of alternative mechanism of telomere length maintenance - Kollár, Richard; Bod'ová, Katarína; Nosek, Jozef; Tomáška, Ľubomír (Physical Review E Statistical Nonlinear and Soft Matter Physics)
Biopolymer length regulation is a complex process that involves a large number of biological, chemical, and physical subprocesses acting simultaneously across multiple spatial and temporal scales. An illustrative example important for genomic stability is the length regulation of telomeres - nucleoprotein structures at the ends of linear chromosomes consisting of tandemly repeated DNA sequences and a specialized set of proteins. Maintenance of telomeres is often facilitated by the enzyme telomerase but, particularly in telomerase-free systems, the maintenance of chromosomal termini depends on alternative lengthening of telomeres (ALT) mechanisms mediated by recombination. Various linear and circular DNA structures were identified to participate in ALT, however, dynamics of the whole process is still poorly understood. We propose a chemical kinetics model of ALT with kinetic rates systematically derived from the biophysics of DNA diffusion and looping. The reaction system is reduced to a coagulation-fragmentation system by quasi-steady-state approximation. The detailed treatment of kinetic rates yields explicit formulas for expected size distributions of telomeres that demonstrate the key role played by the J factor, a quantitative measure of bending of polymers. The results are in agreement with experimental data and point out interesting phenomena: an appearance of very long telomeric circles if the total telomere density exceeds a critical value (excess mass) and a nonlinear response of the telomere size distributions to the amount of telomeric DNA in the system. The results can be of general importance for understanding dynamics of telomeres in telomerase-independent systems as this mode of telomere maintenance is similar to the situation in tumor cells lacking telomerase activity. Furthermore, due to its universality, the model may also serve as a prototype of an interaction between linear and circular DNA structures in various settings.

Insights into the localization and function of the membrane trafficking regulator GNOM ARF-GEF at the Golgi apparatus in Arabidopsis - Naramoto, Satoshi; Otegui, Marisa; Kutsuna, Natsumaro; De Rycke, Riet; Dainobu, Tomoko; Karampelias, Michael; Fujimoto, Masaru; Feraru, Elena; Miki, Daisuke; Fukuda, Hiroo; Nakano, Akihiko; Friml, Jirí (Plant Cell)
GNOM is one of the most characterized membrane trafficking regulators in plants, with crucial roles in development. GNOM encodes an ARF-guanine nucleotide exchange factor (ARF-GEF) that activates small GTPases of the ARF (ADP ribosylation factor) class to mediate vesicle budding at endomembranes. The crucial role of GNOM in recycling of PIN auxin transporters and other proteins to the plasma membrane was identified in studies using the ARF-GEF inhibitor brefeldin A (BFA). GNOM, the most prominent regulator of recycling in plants, has been proposed to act and localize at so far elusive recycling endosomes. Here, we report the GNOM localization in context of its cellular function in Arabidopsis thaliana. State-of-the-art imaging, pharmacological interference, and ultrastructure analysis show that GNOM predominantly localizes to Golgi apparatus. Super-resolution confocal live imaging microscopy identified GNOM and its closest homolog GNOM-like 1 at distinct subdomains on Golgi cisternae. Short-term BFA treatment stabilizes GNOM at the Golgi apparatus, whereas prolonged exposures results in GNOM translocation to trans-Golgi network (TGN)/early endosomes (EEs). Malformed TGN/EE in gnom mutants suggests a role for GNOM in maintaining TGN/EE function. Our results redefine the subcellular action of GNOM and reevaluate the identity and function of recycling endosomes in plants.

Par3-mInsc and Gα i3 cooperate to promote oriented epidermal cell divisions through LGN - Williams, Scott; Ratliff, Lyndsay; Postiglione, Maria P; Knoblich, Juergen; Fuchs, Elaine (Nature Cell Biology)
Asymmetric cell divisions allow stem cells to balance proliferation and differentiation. During embryogenesis, murine epidermis expands rapidly from a single layer of unspecified basal layer progenitors to a stratified, differentiated epithelium. Morphogenesis involves perpendicular (asymmetric) divisions and the spindle orientation protein LGN, but little is known about how the apical localization of LGN is regulated. Here, we combine conventional genetics and lentiviral-mediated in vivo RNAi to explore the functions of the LGN-interacting proteins Par3, mInsc and Gα i3. Whereas loss of each gene alone leads to randomized division angles, combined loss of Gnai3 and mInsc causes a phenotype of mostly planar divisions, akin to loss of LGN. These findings lend experimental support for the hitherto untested model that Par3-mInsc and Gα i3 act cooperatively to polarize LGN and promote perpendicular divisions. Finally, we uncover a developmental switch between delamination-driven early stratification and spindle-orientation-dependent differentiation that occurs around E15, revealing a two-step mechanism underlying epidermal maturation.

Large-scale point-cloud visualization through localized textured surface reconstruction - Arikan, Murat; Preiner, Reinhold; Scheiblauer, Claus; Jeschke, Stefan; Wimmer, Michael (IEEE Transactions on Visualization and Computer Graphics)
In this paper, we introduce a novel scene representation for the visualization of large-scale point clouds accompanied by a set of high-resolution photographs. Many real-world applications deal with very densely sampled point-cloud data, which are augmented with photographs that often reveal lighting variations and inaccuracies in registration. Consequently, the high-quality representation of the captured data, i.e., both point clouds and photographs together, is a challenging and time-consuming task. We propose a two-phase approach, in which the first (preprocessing) phase generates multiple overlapping surface patches and handles the problem of seamless texture generation locally for each patch. The second phase stitches these patches at render-time to produce a high-quality visualization of the data. As a result of the proposed localization of the global texturing problem, our algorithm is more than an order of magnitude faster than equivalent mesh-based texturing techniques. Furthermore, since our preprocessing phase requires only a minor fraction of the whole data set at once, we provide maximum flexibility when dealing with growing data sets.

Strichartz inequality for orthonormal functions - Frank, Rupert; Lewin, Mathieu; Lieb, Élliott; Seiringer, Robert (Journal of the European Mathematical Society)
We prove a Strichartz inequality for a system of orthonormal functions, with an optimal behavior of the constant in the limit of a large number of functions. The estimate generalizes the usual Strichartz inequality, in the same fashion as the Lieb-Thirring inequality generalizes the Sobolev inequality. As an application, we consider the Schrödinger equation with a time-dependent potential and we show the existence of the wave operator in Schatten spaces.

The fitness costs of adaptation via phenotypic plasticity and maternal effects - Ezard, Thomas; Prizak, Roshan; Hoyle, Rebecca (Functional Ecology)
Summary: Phenotypes are often environmentally dependent, which requires organisms to track environmental change. The challenge for organisms is to construct phenotypes using the most accurate environmental cue. Here, we use a quantitative genetic model of adaptation by additive genetic variance, within- and transgenerational plasticity via linear reaction norms and indirect genetic effects respectively. We show how the relative influence on the eventual phenotype of these components depends on the predictability of environmental change (fast or slow, sinusoidal or stochastic) and the developmental lag τ between when the environment is perceived and when selection acts. We then decompose expected mean fitness into three components (variance load, adaptation and fluctuation load) to study the fitness costs of within- and transgenerational plasticity. A strongly negative maternal effect coefficient m minimizes the variance load, but a strongly positive m minimises the fluctuation load. The adaptation term is maximized closer to zero, with positive or negative m preferred under different environmental scenarios. Phenotypic plasticity is higher when τ is shorter and when the environment changes frequently between seasonal extremes. Expected mean population fitness is highest away from highest observed levels of phenotypic plasticity. Within- and transgenerational plasticity act in concert to deliver well-adapted phenotypes, which emphasizes the need to study both simultaneously when investigating phenotypic evolution.

Optimality of non-adaptive strategies: The case of parallel games - Demay, Grégory; Gazi, Peter; Maurer, Ueli; Tackmann, Björn (IEEE International Symposium on Information Theory)
Most cryptographic security proofs require showing that two systems are indistinguishable. A central tool in such proofs is that of a game, where winning the game means provoking a certain condition, and it is shown that the two systems considered cannot be distinguished unless this condition is provoked. Upper bounding the probability of winning such a game, i.e., provoking this condition, for an arbitrary strategy is usually hard, except in the special case where the best strategy for winning such a game is known to be non-adaptive. A sufficient criterion for ensuring the optimality of non-adaptive strategies is that of conditional equivalence to a system, a notion introduced in [1]. In this paper, we show that this criterion is not necessary to ensure the optimality of non-adaptive strategies by giving two results of independent interest: 1) the optimality of non-adaptive strategies is not preserved under parallel composition; 2) in contrast, conditional equivalence is preserved under parallel composition.

The rate of adaptation in large sexual populations with linear chromosomes - Weissman, Daniel; Hallatschek, Oskar (Genetics)
In large populations, multiple beneficial mutations may be simultaneously spreading. In asexual populations, these mutations must either arise on the same background or compete against each other. In sexual populations, recombination can bring together beneficial alleles from different backgrounds, but tightly linked alleles may still greatly interfere with each other. We show for well-mixed populations that when this interference is strong, the genome can be seen as consisting of many effectively asexual stretches linked together. The rate at which beneficial alleles fix is thus roughly proportional to the rate of recombination and depends only logarithmically on the mutation supply and the strength of selection. Our scaling arguments also allow us to predict, with reasonable accuracy, the fitness distribution of fixed mutations when the mutational effect sizes are broad. We focus on the regime in which crossovers occur more frequently than beneficial mutations, as is likely to be the case for many natural populations.

Exome sequencing links corticospinal motor neuron disease to common neurodegenerative disorders - Novarino, Gaia; Fenstermaker, Ali; Zaki, Maha; Hofree, Matan; Silhavy, Jennifer; Heiberg, Andrew; Abdellateef, Mostafa; Rosti, Başak; Scott, Eric; Mansour, Lobna; Masri, Amira; Kayserili, Hülya; et al. (Science)
Hereditary spastic paraplegias (HSPs) are neurodegenerative motor neuron diseases characterized by progressive age-dependent loss of corticospinal motor tract function. Although the genetic basis is partly understood, only a fraction of cases can receive a genetic diagnosis, and a global view of HSP is lacking. By using whole-exome sequencing in combination with network analysis, we identified 18 previously unknown putative HSP genes and validated nearly all of these genes functionally or genetically. The pathways highlighted by these mutations link HSP to cellular transport, nucleotide metabolism, and synapse and axon development. Network analysis revealed a host of further candidate genes, of which three were mutated in our cohort. Our analysis links HSP to other neurodegenerative disorders and can facilitate gene discovery and mechanistic understanding of disease.

Cell surface ABP1-TMK auxin sensing complex activates ROP GTPase signaling - Xu, Tongda; Dai, Ning; Chen, Jisheng; Nagawa, Shingo; Cao, Min; Li, Hongjiang; Zhou, Zimin; Chen, Xu; De Rycke, Riet; Rakusová, Hana; Wang, Wen; Jones, Alan; et al. (Science)
Auxin-binding protein 1 (ABP1) was discovered nearly 40 years ago and was shown to be essential for plant development and morphogenesis, but its mode of action remains unclear. Here, we report that the plasma membrane-localized transmembrane kinase (TMK) receptor-like kinases interact with ABP1 and transduce auxin signal to activate plasma membrane-associated ROPs [Rho-like guanosine triphosphatases (GTPase) from plants], leading to changes in the cytoskeleton and the shape of leaf pavement cells in Arabidopsis. The interaction between ABP1 and TMK at the cell surface is induced by auxin and requires ABP1 sensing of auxin. These findings show that TMK proteins and ABP1 form a cell surface auxin perception complex that activates ROP signaling pathways, regulating nontranscriptional cytoplasmic responses and associated fundamental processes.

Distinct cerebellar engrams in short-term and long-term motor learning - Wang, Wen; Nakadate, Kazuhiko; Masugi Tokita, Miwako; Shutoh, Fumihiro; Aziz, Wajeeha; Tarusawa, Etsuko; Lörincz, Andrea; Molnár, Elek; Kesaf, Sebnem; Li, Yunqing; Fukazawa, Yugo; Nagao, Soichi; et al. (PNAS)
Cerebellar motor learning is suggested to be caused by long-term plasticity of excitatory parallel fiber-Purkinje cell (PF-PC) synapses associated with changes in the number of synaptic AMPA-type glutamate receptors (AMPARs). However, whether the AMPARs decrease or increase in individual PF-PC synapses occurs in physiological motor learning and accounts for memory that lasts over days remains elusive. We combined quantitative SDS-digested freeze-fracture replica labeling for AMPAR and physical dissector electron microscopy with a simple model of cerebellar motor learning, adaptation of horizontal optokinetic response (HOKR) in mouse. After 1-h training of HOKR, short-term adaptation (STA) was accompanied with transient decrease in AMPARs by 28% in target PF-PC synapses. STA was well correlated with AMPAR decrease in individual animals and both STA and AMPAR decrease recovered to basal levels within 24 h. Surprisingly, long-termadaptation (LTA) after five consecutive daily trainings of 1-h HOKR did not alter the number of AMPARs in PF-PC synapses but caused gradual and persistent synapse elimination by 45%, with corresponding PC spine loss by the fifth training day. Furthermore, recovery of LTA after 2 wk was well correlated with increase of PF-PC synapses to the control level. Our findings indicate that the AMPARs decrease in PF-PC synapses and the elimination of these synapses are in vivo engrams in short- and long-term motor learning, respectively, showing a unique type of synaptic plasticity that may contribute to memory consolidation.

Distinct kinetics of synaptic structural plasticity, memory formation, and memory decay in massed and spaced learning - Aziz, Wajeeha; Wang, Wen; Kesaf, Sebnem; Mohamed, Alsayed; Fukazawa, Yugo; Shigemoto, Ryuichi (PNAS)
Long-lasting memories are formed when the stimulus is temporally distributed (spacing effect). However, the synaptic mechanisms underlying this robust phenomenon and the precise time course of the synaptic modifications that occur during learning remain unclear. Here we examined the adaptation of horizontal optokinetic response in mice that underwent 1 h of massed and spaced training at varying intervals. Despite similar acquisition by all training protocols, 1 h of spacing produced the highest memory retention at 24 h, which lasted for 1 mo. The distinct kinetics of memory are strongly correlated with the reduction of floccular parallel fiber-Purkinje cell synapses but not with AMPA receptor (AMPAR) number and synapse size. After the spaced training, we observed 25%, 23%, and 12% reduction in AMPAR density, synapse size, and synapse number, respectively. Four hours after the spaced training, half of the synapses and Purkinje cell spines had been eliminated, whereas AMPAR density and synapse size were recovered in remaining synapses. Surprisingly, massed training also produced long-term memory and halving of synapses; however, this occurred slowly over days, and the memory lasted for only 1 wk. This distinct kinetics of structural plasticity may serve as a basis for unique temporal profiles in the formation and decay of memory with or without intervals.

Existence of ground states for negative ions at the binding threshold - Bellazzini, Jacopo; Frank, Rupert; Lieb, Élliott; Seiringer, Robert (Reviews in Mathematical Physics)
As the nuclear charge Z is continuously decreased an N-electron atom undergoes a binding-unbinding transition. We investigate whether the electrons remain bound and whether the radius of the system stays finite as the critical value Zc is approached. Existence of a ground state at Zc is shown under the condition Zc < N-K, where K is the maximal number of electrons that can be removed at Zc without changing the energy.

A single-molecule approach to explore binding uptake and transport of cancer cell targeting nanotubes - Lamprecht, Constanze; Plochberger, Birgit; Ruprecht, Verena; Wieser, Stefan; Rankl, Christian; Heister, Elena; Unterauer, Barbara; Brameshuber, Mario; Danzberger, Jürgen; Lukanov, Petar; Flahaut, Emmanuel; Schütz, Gerhard; et al. (Nanotechnology)
In the past decade carbon nanotubes (CNTs) have been widely studied as a potential drug-delivery system, especially with functionality for cellular targeting. Yet, little is known about the actual process of docking to cell receptors and transport dynamics after internalization. Here we performed single-particle studies of folic acid (FA) mediated CNT binding to human carcinoma cells and their transport inside the cytosol. In particular, we employed molecular recognition force spectroscopy, an atomic force microscopy based method, to visualize and quantify docking of FA functionalized CNTs to FA binding receptors in terms of binding probability and binding force. We then traced individual fluorescently labeled, FA functionalized CNTs after specific uptake, and created a dynamic 'roadmap' that clearly showed trajectories of directed diffusion and areas of nanotube confinement in the cytosol. Our results demonstrate the potential of a single-molecule approach for investigation of drug-delivery vehicles and their targeting capacity.

Active elastic thin shell theory for cellular deformations - Berthoumieux, Hélène; Maître, Jean-Léon; Heisenberg, Carl-Philipp J; Paluch, Ewa; Julicher, Frank; Salbreux, Guillaume (New Journal of Physics)
We derive the equations for a thin, axisymmetric elastic shell subjected to an internal active stress giving rise to active tension and moments within the shell. We discuss the stability of a cylindrical elastic shell and its response to a localized change in internal active stress. This description is relevant to describe the cellular actomyosin cortex, a thin shell at the cell surface behaving elastically at a short timescale and subjected to active internal forces arising from myosin molecular motor activity. We show that the recent observations of cell deformation following detachment of adherent cells (Maître J-L et al 2012 Science 338 253-6) are well accounted for by this mechanical description. The actin cortex elastic and bending moduli can be obtained from a quantitative analysis of cell shapes observed in these experiments. Our approach thus provides a non-invasive, imaging-based method for the extraction of cellular physical parameters.

Bipolar plasma membrane distribution of phosphoinositides and their requirement for auxin-mediated cell polarity and patterning in Arabidopsis - Tejos, Ricardo; Sauer, Michael; Vanneste, Steffen; Palacios-Gomez, MiriamPalacios; Li, Hongjiang; Heilmann, Mareike; Van Wijk, Ringo; Vermeer, Joop; Heilmann, Ingo; Munnik, Teun; Friml, Jirí (Plant Cell)
Cell polarity manifested by asymmetric distribution of cargoes, such as receptors and transporters, within the plasma membrane (PM) is crucial for essential functions in multicellular organisms. In plants, cell polarity (re)establishment is intimately linked to patterning processes. Despite the importance of cell polarity, its underlying mechanisms are still largely unknown, including the definition and distinctiveness of the polar domains within the PM. Here, we show in Arabidopsis thaliana that the signaling membrane components, the phosphoinositides phosphatidylinositol 4-phosphate (PtdIns4P) and phosphatidylinositol 4, 5-bisphosphate [PtdIns(4, 5)P2] as well as PtdIns4P 5-kinases mediating their interconversion, are specifically enriched at apical and basal polar plasma membrane domains. The PtdIns4P 5-kinases PIP5K1 and PIP5K2 are redundantly required for polar localization of specifically apical and basal cargoes, such as PIN-FORMED transporters for the plant hormone auxin. As a consequence of the polarity defects, instructive auxin gradients as well as embryonic and postembryonic patterning are severely compromised. Furthermore, auxin itself regulates PIP5K transcription and PtdIns4P and PtdIns(4, 5)P2 levels, in particular their association with polar PM domains. Our results provide insight into the polar domain-delineating mechanisms in plant cells that depend on apical and basal distribution of membrane lipids and are essential for embryonic and postembryonic patterning.

Adaptive security of constrained PRFs - Georg Fuchsbauer; Konstantinov, Momchil; Krzysztof Pietrzak; Rao, Vanishree
Constrained pseudorandom functions have recently been introduced independently by Boneh and Waters (Asiacrypt’13), Kiayias et al. (CCS’13), and Boyle et al. (PKC’14). In a standard pseudorandom function (PRF) a key k is used to evaluate the PRF on all inputs in the domain. Constrained PRFs additionally offer the functionality to delegate “constrained” keys kS which allow to evaluate the PRF only on a subset S of the domain. The three above-mentioned papers all show that the classical GGM construction (J.ACM’86) of a PRF from a pseudorandom generator (PRG) directly yields a constrained PRF where one can compute constrained keys to evaluate the PRF on all inputs with a given prefix. This constrained PRF has already found many interesting applications. Unfortunately, the existing security proofs only show selective security (by a reduction to the security of the underlying PRG). To achieve full security, one has to use complexity leveraging, which loses an exponential factor 2N in security, where N is the input length. The first contribution of this paper is a new reduction that only loses a quasipolynomial factor qlog N, where q is the number of adversarial queries. For this we develop a new proof technique which constructs a distinguisher by interleaving simple guessing steps and hybrid arguments a small number of times. This approach might be of interest also in other contexts where currently the only technique to achieve full security is complexity leveraging. Our second contribution is concerned with another constrained PRF, due to Boneh and Waters, which allows for constrained keys for the more general class of bit-fixing functions. Their security proof also suffers from a 2N loss, which we show is inherent. We construct a meta-reduction which shows that any “simple” reduction of full security from a noninteractive hardness assumption must incur an exponential security loss.

Absolutely continuous spectrum for random Schrödinger operators on the Fibonacci and similar Tree-strips - Sadel, Christian (Mathematical Physics, Analysis and Geometry)
We consider cross products of finite graphs with a class of trees that have arbitrarily but finitely long line segments, such as the Fibonacci tree. Such cross products are called tree-strips. We prove that for small disorder random Schrödinger operators on such tree-strips have purely absolutely continuous spectrum in a certain set.

Formation of stripes and slabs near the ferromagnetic transition - Giuliani, Alessandro; Lieb, Élliott; Seiringer, Robert (Communications in Mathematical Physics)
We consider Ising models in d = 2 and d = 3 dimensions with nearest neighbor ferromagnetic and long-range antiferromagnetic interactions, the latter decaying as (distance)-p, p > 2d, at large distances. If the strength J of the ferromagnetic interaction is larger than a critical value J c, then the ground state is homogeneous. It has been conjectured that when J is smaller than but close to J c, the ground state is periodic and striped, with stripes of constant width h = h(J), and h → ∞ as J → Jc -. (In d = 3 stripes mean slabs, not columns.) Here we rigorously prove that, if we normalize the energy in such a way that the energy of the homogeneous state is zero, then the ratio e 0(J)/e S(J) tends to 1 as J → Jc -, with e S(J) being the energy per site of the optimal periodic striped/slabbed state and e 0(J) the actual ground state energy per site of the system. Our proof comes with explicit bounds on the difference e 0(J)-e S(J) at small but positive J c-J, and also shows that in this parameter range the ground state is striped/slabbed in a certain sense: namely, if one looks at a randomly chosen window, of suitable size ℓ (very large compared to the optimal stripe size h(J)), one finds a striped/slabbed state with high probability.

An arms race between producers and scroungers can drive the evolution of social cognition - Arbilly, Michal; Weissman, Daniel; Feldman, Marcus; Grodzinski, Uri (Behavioral Ecology)
The social intelligence hypothesis states that the need to cope with complexities of social life has driven the evolution of advanced cognitive abilities. It is usually invoked in the context of challenges arising from complex intragroup structures, hierarchies, and alliances. However, a fundamental aspect of group living remains largely unexplored as a driving force in cognitive evolution: the competition between individuals searching for resources (producers) and conspecifics that parasitize their findings (scroungers). In populations of social foragers, abilities that enable scroungers to steal by outsmarting producers, and those allowing producers to prevent theft by outsmarting scroungers, are likely to be beneficial and may fuel a cognitive arms race. Using analytical theory and agent-based simulations, we present a general model for such a race that is driven by the producer-scrounger game and show that the race's plausibility is dramatically affected by the nature of the evolving abilities. If scrounging and scrounging avoidance rely on separate, strategy-specific cognitive abilities, arms races are short-lived and have a limited effect on cognition. However, general cognitive abilities that facilitate both scrounging and scrounging avoidance undergo stable, long-lasting arms races. Thus, ubiquitous foraging interactions may lead to the evolution of general cognitive abilities in social animals, without the requirement of complex intragroup structures.

Cryptic genetic variation can make "irreducible complexity" a common mode of adaptation in sexual populations - Trotter, Meredith; Weissman, Daniel; Peterson, Grant; Peck, Kayla; Masel, Joanna (Evolution)
The existence of complex (multiple-step) genetic adaptations that are "irreducible" (i.e., all partial combinations are less fit than the original genotype) is one of the longest standing problems in evolutionary biology. In standard genetics parlance, these adaptations require the crossing of a wide adaptive valley of deleterious intermediate stages. Here, we demonstrate, using a simple model, that evolution can cross wide valleys to produce "irreducibly complex" adaptations by making use of previously cryptic mutations. When revealed by an evolutionary capacitor, previously cryptic mutants have higher initial frequencies than do new mutations, bringing them closer to a valley-crossing saddle in allele frequency space. Moreover, simple combinatorics implies an enormous number of candidate combinations exist within available cryptic genetic variation. We model the dynamics of crossing of a wide adaptive valley after a capacitance event using both numerical simulations and analytical approximations. Although individual valley crossing events become less likely as valleys widen, by taking the combinatorics of genotype space into account, we see that revealing cryptic variation can cause the frequent evolution of complex adaptations.

Emergence of task-dependent representations in working memory circuits - Savin, Cristina; Triesch, Jochen (Frontiers in Computational Neuroscience)
A wealth of experimental evidence suggests that working memory circuits preferentially represent information that is behaviorally relevant. Still, we are missing a mechanistic account of how these representations come about. Here we provide a simple explanation for a range of experimental findings, in light of prefrontal circuits adapting to task constraints by reward-dependent learning. In particular, we model a neural network shaped by reward-modulated spike-timing dependent plasticity (r-STDP) and homeostatic plasticity (intrinsic excitability and synaptic scaling). We show that the experimentally-observed neural representations naturally emerge in an initially unstructured circuit as it learns to solve several working memory tasks. These results point to a critical, and previously unappreciated, role for reward-dependent learning in shaping prefrontal cortex activity.

Edge universality of beta ensembles - Bourgade, Paul; Erdös, László; Yau, Horngtzer (Communications in Mathematical Physics)
We prove the edge universality of the beta ensembles for any β ≥ 1, provided that the limiting spectrum is supported on a single interval, and the external potential is C4 and regular. We also prove that the edge universality holds for generalized Wigner matrices for all symmetry classes. Moreover, our results allow us to extend bulk universality for beta ensembles from analytic potentials to potentials in class C4.

Bimodal regulation of ICR1 levels generates self-organizing auxin distribution - Hazak, Ora; Obolski, Uri; Prat, Tomas; Friml, Jiří; Hadany, Lilach; Yalovsky, Shaul (PNAS)
Auxin polar transport, local maxima, and gradients have become an importantmodel system for studying self-organization. Auxin distribution is regulated by auxin-dependent positive feedback loops that are not well-understood at the molecular level. Previously, we showed the involvement of the RHO of Plants (ROP) effector INTERACTOR of CONSTITUTIVELY active ROP 1 (ICR1) in regulation of auxin transport and that ICR1 levels are posttranscriptionally repressed at the site of maximum auxin accumulation at the root tip. Here, we show that bimodal regulation of ICR1 levels by auxin is essential for regulating formation of auxin local maxima and gradients. ICR1 levels increase concomitant with increase in auxin response in lateral root primordia, cotyledon tips, and provascular tissues. However, in the embryo hypophysis and root meristem, when auxin exceeds critical levels, ICR1 is rapidly destabilized by an SCF(TIR1/AFB) [SKP, Cullin, F-box (transport inhibitor response 1/auxin signaling F-box protein)]-dependent auxin signaling mechanism. Furthermore, ectopic expression of ICR1 in the embryo hypophysis resulted in reduction of auxin accumulation and concomitant root growth arrest. ICR1 disappeared during root regeneration and lateral root initiation concomitantly with the formation of a local auxin maximum in response to external auxin treatments and transiently after gravitropic stimulation. Destabilization of ICR1 was impaired after inhibition of auxin transport and signaling, proteasome function, and protein synthesis. A mathematical model based on these findings shows that an in vivo-like auxin distribution, rootward auxin flux, and shootward reflux can be simulated without assuming preexisting tissue polarity. Our experimental results and mathematical modeling indicate that regulation of auxin distribution is tightly associated with auxin-dependent ICR1 levels.

Fabry-Perot interferometer with quantum mirrors: Nonlinear light transport and rectification - Fratini, Filippo; Mascarenhas, Eduardo; Safari, Laleh; Poizat, Jean; Valente, Daniel; Auffèves, Alexia; Gerace, Dario; Santos, Marcelo (Physical Review Letters)
Optical transport represents a natural route towards fast communications, and it is currently used in large scale data transfer. The progressive miniaturization of devices for information processing calls for the microscopic tailoring of light transport and confinement at length scales appropriate for upcoming technologies. With this goal in mind, we present a theoretical analysis of a one-dimensional Fabry-Perot interferometer built with two highly saturable nonlinear mirrors: a pair of two-level systems. Our approach captures nonlinear and nonreciprocal effects of light transport that were not reported previously. Remarkably, we show that such an elementary device can operate as a microscopic integrated optical rectifier.

Action potential modulation in CA1 pyramidal neuron axons facilitates OLM interneuron activation in recurrent inhibitory microcircuits of rat hippocampus - Kim, Sooyun (PLoS One)
Oriens-lacunosum moleculare (O-LM) interneurons in the CA1 region of the hippocampus play a key role in feedback inhibition and in the control of network activity. However, how these cells are efficiently activated in the network remains unclear. To address this question, I performed recordings from CA1 pyramidal neuron axons, the presynaptic fibers that provide feedback innervation of these interneurons. Two forms of axonal action potential (AP) modulation were identified. First, repetitive stimulation resulted in activity-dependent AP broadening. Broadening showed fast onset, with marked changes in AP shape following a single AP. Second, tonic depolarization in CA1 pyramidal neuron somata induced AP broadening in the axon, and depolarization-induced broadening summated with activity-dependent broadening. Outsideout patch recordings from CA1 pyramidal neuron axons revealed a high density of a-dendrotoxin (α-DTX)-sensitive, inactivating K+ channels, suggesting that K+ channel inactivation mechanistically contributes to AP broadening. To examine the functional consequences of axonal AP modulation for synaptic transmission, I performed paired recordings between synaptically connected CA1 pyramidal neurons and O-LM interneurons. CA1 pyramidal neuron-O-LM interneuron excitatory postsynaptic currents (EPSCs) showed facilitation during both repetitive stimulation and tonic depolarization of the presynaptic neuron. Both effects were mimicked and occluded by α-DTX, suggesting that they were mediated by K+ channel inactivation. Therefore, axonal AP modulation can greatly facilitate the activation of O-LM interneurons. In conclusion, modulation of AP shape in CA1 pyramidal neuron axons substantially enhances the efficacy of principal neuron-interneuron synapses, promoting the activation of O-LM interneurons in recurrent inhibitory microcircuits.

Scalable privacy-preserving data sharing methodology for genome-wide association studies - Yu, Fei; Fienberg, Stephen; Slaković, Alexandra; Uhler, Caroline (Journal of Biomedical Informatics)
The protection of privacy of individual-level information in genome-wide association study (GWAS) databases has been a major concern of researchers following the publication of “an attack” on GWAS data by Homer et al. (2008). Traditional statistical methods for confidentiality and privacy protection of statistical databases do not scale well to deal with GWAS data, especially in terms of guarantees regarding protection from linkage to external information. The more recent concept of differential privacy, introduced by the cryptographic community, is an approach that provides a rigorous definition of privacy with meaningful privacy guarantees in the presence of arbitrary external information, although the guarantees may come at a serious price in terms of data utility. Building on such notions, Uhler et al. (2013) proposed new methods to release aggregate GWAS data without compromising an individual’s privacy. We extend the methods developed in Uhler et al. (2013) for releasing differentially-private χ2χ2-statistics by allowing for arbitrary number of cases and controls, and for releasing differentially-private allelic test statistics. We also provide a new interpretation by assuming the controls’ data are known, which is a realistic assumption because some GWAS use publicly available data as controls. We assess the performance of the proposed methods through a risk-utility analysis on a real data set consisting of DNA samples collected by the Wellcome Trust Case Control Consortium and compare the methods with the differentially-private release mechanism proposed by Johnson and Shmatikov (2013).

gIPFrm: Generalized iterative proportional fitting for relational models - Klimova, Anna; Rudas, Tamás
Maximum likelihood estimation under relational models, with or without the overall effect. For more information see the reference manual

Netrin-G/NGL complexes encode functional synaptic diversification - Matsukawa, Hiroshi; Akiyoshi Nishimura, Sachiko; Zhang, Qi; Luján, Rafael; Yamaguchi, Kazuhiko; Goto, Hiromichi; Yaguchi, Kunio; Hashikawa, Tsutomu; Sano, Chie; Shigemoto, Ryuichi; Nakashiba, Toshiaki; Itohara, Shigeyoshi (Journal of Neuroscience)
Synaptic cell adhesion molecules are increasingly gaining attention for conferring specific properties to individual synapses. Netrin-G1 and netrin-G2 are trans-synaptic adhesion molecules that distribute on distinct axons, and their presence restricts the expression of their cognate receptors, NGL1 and NGL2, respectively, to specific subdendritic segments of target neurons. However, the neural circuits and functional roles of netrin-G isoform complexes remain unclear. Here, we use netrin-G-KO and NGL-KO mice to reveal that netrin-G1/NGL1 and netrin-G2/NGL2 interactions specify excitatory synapses in independent hippocampal pathways. In the hippocampal CA1 area, netrin-G1/NGL1 and netrin-G2/NGL2 were expressed in the temporoammonic and Schaffer collateral pathways, respectively. The lack of presynaptic netrin-Gs led to the dispersion of NGLs from postsynaptic membranes. In accord, netrin-G mutant synapses displayed opposing phenotypes in long-term and short-term plasticity through discrete biochemical pathways. The plasticity phenotypes in netrin-G-KOs were phenocopied in NGL-KOs, with a corresponding loss of netrin-Gs from presynaptic membranes. Our findings show that netrin-G/NGL interactions differentially control synaptic plasticity in distinct circuits via retrograde signaling mechanisms and explain how synaptic inputs are diversified to control neuronal activity.

Phase transition in the density of states of quantum spin glasses - Erdös, László; Schröder, Dominik J (Mathematical Physics, Analysis and Geometry)
We prove that the empirical density of states of quantum spin glasses on arbitrary graphs converges to a normal distribution as long as the maximal degree is negligible compared with the total number of edges. This extends the recent results of Keating et al. (2014) that were proved for graphs with bounded chromatic number and with symmetric coupling distribution. Furthermore, we generalise the result to arbitrary hypergraphs. We test the optimality of our condition on the maximal degree for p-uniform hypergraphs that correspond to p-spin glass Hamiltonians acting on n distinguishable spin- 1/2 particles. At the critical threshold p = n1/2 we find a sharp classical-quantum phase transition between the normal distribution and the Wigner semicircle law. The former is characteristic to classical systems with commuting variables, while the latter is a signature of noncommutative random matrix theory.

Hypersurfaces and their singularities in partial correlation testing - Lin, Shaowei; Uhler, Caroline; Sturmfels, Bernd; Bühlmann, Peter (Foundations of Computational Mathematics)
An asymptotic theory is developed for computing volumes of regions in the parameter space of a directed Gaussian graphical model that are obtained by bounding partial correlations. We study these volumes using the method of real log canonical thresholds from algebraic geometry. Our analysis involves the computation of the singular loci of correlation hypersurfaces. Statistical applications include the strong-faithfulness assumption for the PC algorithm and the quantification of confounder bias in causal inference. A detailed analysis is presented for trees, bow ties, tripartite graphs, and complete graphs.

Exact formulas for the normalizing constants of Wishart distributions for graphical models - Caroline Uhler; Lenkoski, Alex; Richards, Donald (ArXiv)
Gaussian graphical models have received considerable attention during the past four decades from the statistical and machine learning communities. In Bayesian treatments of this model, the G-Wishart distribution serves as the conjugate prior for inverse covariance matrices satisfying graphical constraints. While it is straightforward to posit the unnormalized densities, the normalizing constants of these distributions have been known only for graphs that are chordal, or decomposable. Up until now, it was unknown whether the normalizing constant for a general graph could be represented explicitly, and a considerable body of computational literature emerged that attempted to avoid this apparent intractability. We close this question by providing an explicit representation of the G-Wishart normalizing constant for general graphs.

Deterministic progenitor behavior and unitary production of neurons in the neocortex - Gao, Peng; Postiglione, Maria P; Krieger, Teresa; Hernandez, Luisirene; Wang, Chao; Han, Zhi; Streicher, Carmen; Papusheva, Ekaterina; Insolera, Ryan; Chugh, Kritika; Kodish, Oren; Huang, Kun; et al. (Cell)
Radial glial progenitors (RGPs) are responsible for producing nearly all neocortical neurons. To gain insight into the patterns of RGP division and neuron production, we quantitatively analyzed excitatory neuron genesis in the mouse neocortex using Mosaic Analysis with Double Markers, which provides single-cell resolution of progenitor division patterns and potential in vivo. We found that RGPs progress through a coherent program in which their proliferative potential diminishes in a predictable manner. Upon entry into the neurogenic phase, individual RGPs produce ∼8–9 neurons distributed in both deep and superficial layers, indicating a unitary output in neuronal production. Removal of OTX1, a transcription factor transiently expressed in RGPs, results in both deep- and superficial-layer neuron loss and a reduction in neuronal unit size. Moreover, ∼1/6 of neurogenic RGPs proceed to produce glia. These results suggest that progenitor behavior and histogenesis in the mammalian neocortex conform to a remarkably orderly and deterministic program.

Dendrite morphogenesis depends on relative levels of NT-3/TrkC signaling - William, Joo; Hippenmeyer, Simon; Luo, Liqun (Science)
Neurotrophins regulate diverse aspects of neuronal development and plasticity, but their precise in vivo functions during neural circuit assembly in the central brain remain unclear. We show that the neurotrophin receptor tropomyosin-related kinase C (TrkC) is required for dendritic growth and branching of mouse cerebellar Purkinje cells. Sparse TrkC knockout reduced dendrite complexity, but global Purkinje cell knockout had no effect. Removal of the TrkC ligand neurotrophin-3 (NT-3) from cerebellar granule cells, which provide major afferent input to developing Purkinje cell dendrites, rescued the dendrite defects caused by sparse TrkC disruption in Purkinje cells. Our data demonstrate that NT-3 from presynaptic neurons (granule cells) is required for TrkC-dependent competitive dendrite morphogenesis in postsynaptic neurons (Purkinje cells)—a previously unknown mechanism of neural circuit development.

Verification of markov decision processes using learning algorithms - Brázdil, Tomáš; Chatterjee, Krishnendu; Chmelik, Martin; Forejt, Vojtěch; Kretinsky, Jan; Kwiatkowska, Marta; Parker, David; Ujma, Mateusz (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics))
We present a general framework for applying machine-learning algorithms to the verification of Markov decision processes (MDPs). The primary goal of these techniques is to improve performance by avoiding an exhaustive exploration of the state space. Our framework focuses on probabilistic reachability, which is a core property for verification, and is illustrated through two distinct instantiations. The first assumes that full knowledge of the MDP is available, and performs a heuristic-driven partial exploration of the model, yielding precise lower and upper bounds on the required probability. The second tackles the case where we may only sample the MDP, and yields probabilistic guarantees, again in terms of both the lower and upper bounds, which provides efficient stopping criteria for the approximation. The latter is the first extension of statistical model checking for unbounded properties inMDPs. In contrast with other related techniques, our approach is not restricted to time-bounded (finite-horizon) or discounted properties, nor does it assume any particular properties of the MDP. We also show how our methods extend to LTL objectives. We present experimental results showing the performance of our framework on several examples.

Nanodomain coupling explains Ca^2+ independence of transmitter release time course at a fast central synapse - Arai, Itaru; Jonas, Peter M (eLife)
A puzzling property of synaptic transmission, originally established at the neuromuscular junction, is that the time course of transmitter release is independent of the extracellular Ca2+ concentration ([Ca2+]o), whereas the rate of release is highly [Ca2+]o-dependent. Here, we examine the time course of release at inhibitory basket cell-Purkinje cell synapses and show that it is independent of [Ca2+]o. Modeling of Ca2+-dependent transmitter release suggests that the invariant time course of release critically depends on tight coupling between Ca2+ channels and release sensors. Experiments with exogenous Ca2+ chelators reveal that channel-sensor coupling at basket cell-Purkinje cell synapses is very tight, with a mean distance of 10–20 nm. Thus, tight channel-sensor coupling provides a mechanistic explanation for the apparent [Ca2+]o independence of the time course of release.

Bifurcation of the endocytic pathway into Rab5-dependent and -independent transport to the vacuole - Toshima, Junko; Nishinoaki, Show; Sato, Yoshifumi; Yamamoto, Wataru; Furukawa, Daiki; Siekhaus, Daria E; Sawaguchi, Akira; Toshima, Jiro (Nature Communications)
The yeast Rab5 homologue, Vps21p, is known to be involved both in the vacuolar protein sorting (VPS) pathway from the trans-Golgi network to the vacuole, and in the endocytic pathway from the plasma membrane to the vacuole. However, the intracellular location at which these two pathways converge remains unclear. In addition, the endocytic pathway is not completely blocked in yeast cells lacking all Rab5 genes, suggesting the existence of an unidentified route that bypasses the Rab5-dependent endocytic pathway. Here we show that convergence of the endocytic and VPS pathways occurs upstream of the requirement for Vps21p in these pathways. We also identify a previously unidentified endocytic pathway mediated by the AP-3 complex. Importantly, the AP-3-mediated pathway appears mostly intact in Rab5-disrupted cells, and thus works as an alternative route to the vacuole/lysosome. We propose that the endocytic traffic branches into two routes to reach the vacuole: a Rab5-dependent VPS pathway and a Rab5-independent AP-3-mediated pathway.

Characterizing spiking in noisy type II neurons - Bodova, Katarina; Paydarfar, David; Forger, Daniel (Journal of Theoretical Biology)
Understanding the dynamics of noisy neurons remains an important challenge in neuroscience. Here, we describe a simple probabilistic model that accurately describes the firing behavior in a large class (type II) of neurons. To demonstrate the usefulness of this model, we show how it accurately predicts the interspike interval (ISI) distributions, bursting patterns and mean firing rates found by: (1) simulations of the classic Hodgkin-Huxley model with channel noise, (2) experimental data from squid giant axon with a noisy input current and (3) experimental data on noisy firing from a neuron within the suprachiasmatic nucleus (SCN). This simple model has 6 parameters, however, in some cases, two of these parameters are coupled and only 5 parameters account for much of the known behavior. From these parameters, many properties of spiking can be found through simple calculation. Thus, we show how the complex effects of noise can be understood through a simple and general probabilistic model.

Validity of spin-wave theory for the quantum Heisenberg model - Correggi, Michele; Giuliani, Alessandro; Seiringer, Robert (EPL)
Spin-wave theory is a key ingredient in our comprehension of quantum spin systems, and is used successfully for understanding a wide range of magnetic phenomena, including magnon condensation and stability of patterns in dipolar systems. Nevertheless, several decades of research failed to establish the validity of spin-wave theory rigorously, even for the simplest models of quantum spins. A rigorous justification of the method for the three-dimensional quantum Heisenberg ferromagnet at low temperatures is presented here. We derive sharp bounds on its free energy by combining a bosonic formulation of the model introduced by Holstein and Primakoff with probabilistic estimates and operator inequalities.

Mind the nuisance: Gaussian process classification using privileged noise - Hernandez Lobato, Daniel; Sharmanska, Viktoriia; Kersting, Kristian; Lampert, Christoph; Quadrianto, Novi (Advances in Neural Information Processing Systems)
The learning with privileged information setting has recently attracted a lot of attention within the machine learning community, as it allows the integration of additional knowledge into the training process of a classifier, even when this comes in the form of a data modality that is not available at test time. Here, we show that privileged information can naturally be treated as noise in the latent function of a Gaussian process classifier (GPC). That is, in contrast to the standard GPC setting, the latent function is not just a nuisance but a feature: it becomes a natural measure of confidence about the training data by modulating the slope of the GPC probit likelihood function. Extensive experiments on public datasets show that the proposed GPC method using privileged noise, called GPC+, improves over a standard GPC without privileged knowledge, and also over the current state-of-the-art SVM-based method, SVM+. Moreover, we show that advanced neural networks and deep learning methods can be compressed as privileged information.

The optogenetic promise for oncology: Episode I - Inglés Prieto, Álvaro; Gschaider-Reichhart, Eva; Schelch, Karin; Janovjak, Harald L; Grusch, Michael (Molecular and Cellular Oncology)
As light-based control of fundamental signaling pathways is becoming a reality, the field of optogenetics is rapidly moving beyond neuroscience. We have recently developed receptor tyrosine kinases that are activated by light and control cell proliferation, epithelial–mesenchymal transition, and angiogenic sprouting—cell behaviors central to cancer progression.